Long-term stability of NH3-SCR catalysts in the presence of high NO2 concentrations and the performance of a modified V-W-Mo catalyst - Bo Yu; Qichao Li; Shuran Zhou; Heng Yang; Xingyu Liu; Hanjun Lu; Zhongwei Wang; Li Yang; Fang Liu (Fuel, 2027)

From repeat-pass to single-pass: City-scale 3D point-cloud reconstruction via InSAR-TomoSAR fusion with the Hongtu-1 multistatic SAR constellation - Yulun Wu; Heng Zhang; Jili Wang; Yunkai Deng; Ruizhe Liu; Qing Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A free-view registration network with geometric generation for unrestricted pig body size measurement - Heng Liu; Yuqing Zou; Shuyan Su; Xiying Li (Computers and Electronics in Agriculture, 2026)

Enhancing herbaceous biomass combustion in an industrial-scale CFB boiler using iron-based oxygen carriers as bed material - Guang Sun; Lin Li; Chong Liu; Tianxin Li; Heng Liu; Lunbo Duan (Fuel, 2026)

DBD/Fe(II)/peracetic acid pretreatment mitigates nanofiltration fouling in landfill leachate treatment via coupled oxidation-coagulation and plasma-assisted iron cycling - Chuanfei Zhang; Wenjun Yin; Zhangjie Yu; Xin Mao; Jinlong Wang; Bin Liu; Xiaobin Tang; Langming Bai; Guibai Li; Heng Liang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Allelochemicals stimulation (ACS) strategy: Potential for studying allelopathy and discovery of phytotoxins - Dan He; Zhibo Hu; Haishan Cui; Cheng Li; Qiang Wang; Heng Guo; Lan Liu; Jing Li (Phytochemistry, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Static magnetic field coupled with magnetic biochar boosts methane production in sludge anaerobic digestion by activating dual electron transfer mechanisms - Likui Feng; Muzi Li; Kaiyi Zhang; Shuo Liu; Heng Liang; Zhelu Gao; Huizhi Mu; Shufei He; Qingliang Zhao; Liangliang Wei (Journal of Environmental Chemical Engineering, 2026)

Flexible superhydrophilic amidoxime-based porous organic polymers linked by amide bonds for highly selective uranium extraction from seawater - Tianrui Li; Heng Zhao; Xiaoying Yuan; Chengjin Xu; Miaomiao Zhang; Chunfeng Li; Xiujing Peng; Xiaolei Liu; Guoxin Sun; Yu Cui (Journal of Environmental Chemical Engineering, 2026)

Multi-active-site engineered g-C3N4 for selective H2O2 photosynthesis and efficient water purification - Ying Meng; Feng Ji; Heng Rao; Jun Li; Zhongyi Liu; Zhiyuan Wang (Journal of Environmental Chemical Engineering, 2026)

Regulated SMA aggregation in PVDF membranes via dual coagulation for enhanced protein binding efficiency - Xuefeng Li; Heng Liu (Journal of Environmental Chemical Engineering, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Poly(thiophene vinylene)-based conjugated polyelectrolytes as anode interlayer materials for efficient and flexible organic solar cells - Zheng Zhang; Heng Liu; Qingyang Li; Yanhe Xiang; Yao Tong; Shouke Yan; Zongrui Wang; Bowei Xu (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Disparity in individual mobility and heat exposure between returners and explorers based on mobile location data - Heng Wu; Yong Liu; Mei Po Kwan; Li Fan; Guangyu Zhang (Building and Environment, 2026)

Tracing microplastics uptake and translocation in plants using aggregation-induced emission materials - Yang Liu; Siqi Yang; Xia Wang; Wei Du; Nan Fu; Penglin Li; Heng Wei; Fen Zhao; Zijie Qiu; Hao Qiu; Yanxu Zhang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Synergistic aerodynamic-atomization regulation strategy for occupational dust hazard control at mechanized coal transfer points - Wen Nie; Xingchao Cha; Lidian Guo; Huitian Peng; Wenjin Niu; Heng Liu; Mingyuan Lu; Jinkun Zhang; Yunshuo Shi; Yuhang Li; Meiyang Liao (Process Safety and Environmental Protection, 2026)

Flotation mechanism of an amide-based fatty acid collector for quartz ore: A gene-matching perspective - Wenda Guo; Baida Chen; Zhenyue Zhang; Sicheng Li; Han Zhang; Heng Zhang; Hanjun Wu; Defeng Liu (Minerals Engineering, 2026)

Regulation of EC precursors in Huangjiu: Multi-omics deciphers the mechanism of synthetic microbial communities - Shufang Tian; Heng Niu; Yuyan Zhang; Guocheng Du; Yuanli Wang; Mengxi Li; Yanbin Li; Qingtao Liu (International Journal of Food Microbiology, 2026)

Chitosan-induced delay in quality deterioration of sturgeon fillets: insights from untargeted metabolomics and microbial diversity profiling under refrigeration - Kai Liu; Zi-Heng Yan; Hao Tao; Dan Zhang; Li-Wen Wang; Chun-Yu Kang (Food Chemistry, 2026)

Chemical vapor deposition grown two-dimensional SnSe2 for dual-mode applications in photodetection and neuromorphic synaptic vision - Xinjian Liu; Weisen Zhang; Wenhao Fan; Mengyang Li; Yu Zhang; Weijie Bai; Heng Li; Shougen Yin; Hui Yan (Chemical Engineering Journal, 2026)

Dual-responsive injectable hydrogel loaded with DPSCs accelerates diabetic wound healing by promoting mitochondrial transfer to reduce senescent cells - Yonghao Liu; Pengcheng Pang; Shangjin Feng; Wanyang Zhong; Juan Wang; Ye Liu; Xiaoyu Zheng; Ziwei Li; Heng Zhou; Yan He; Qingsong Ye (Chemical Engineering Journal, 2026)

A novel lignocellulose-based activated carbon derived from bamboo fibers via urea phosphate activation for high-performance Cr (VI) removal - Heng Liu; Qianying Li; Zhilin Jiang; Baoguo Yang; Dongcheng Chen; Zhigao Liu; Jixin Tang; Lili Li; Xiaoran Deng (Biomass and Bioenergy, 2026)

MBPBERT: A Large Language Model for Metal-Binding Peptide Discovery - Guifen Jian; Xinwei Li; Yu Chen; Junjie Liu; Ziyang Liu; Xing Shang; Heng Chen; Jian Huang; Bifang He (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A dynamic point-association graph method for surface settlement prediction in subway foundation pits: application to Daqiao Station - Tao Kong; Zhen-hua Yang; Qing Tan; Zhao-cheng Liu; Ke Liu; Chuan-dong Yao; Zhen-long Xue; Yu-heng Li (Applied Geophysics, 2026)

EID1 blockade potentiates immunosurveillance against cancer metastasis via FPR1-mediated DC-NK crosstalk - Ziqi Jin; Xiao Zhang; Huijuan Zhang; Siying Qin; Siqi Zhang; Shuqing Zhang; Lin Xia; Peipei Li; Wen Xu; Peng Liu; Liwei Zhao; Ruidong Xue; et al. (Science China Life Sciences, 2026)

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Amino acid functionalization-induced dipole regulation suppresses carrier decay in perylene diimide to enhance photocatalytic activity - Weili Yu; Ningjie Fang; Ruobing Wang; Zhaobing Liu; Jinhui Li; Jieyuan Li; Hongxiang Li; Heng Wang; Jie Xiong; Yinghao Chu (Journal of Hazardous Materials, 2026)

Optimization of dust collector cartridge performance parameters using a porous media model - Huitian Peng; Yuhang Li; Wen Nie; Lidian Guo; Fei Liu; Heng Liu; Mingyuan Lu; Jinkun Zhang; Yunshuo Shi; Meiyang Liao; Xingchao Cha (Fuel, 2026)

Striking a balance: Grain yield and functional substances of black rice (Oryza sativa L.) under shading stress in tropical regions - Shaokun Song; Song Li; Zongli Liu; Yixue Mu; Long Chen; Heng Zhang; Kaiwen Qiu; Lixiao Nie (European Journal of Agronomy, 2026)

Reprogramming senescent granulosa cells for germ-cell generation - Dai Heng; Kairang Jin; Guoxing Yin; Chenglei Tian; Xiaoyan Sheng; Jiangtao Lu; Yiwei Wu; Xiaoying Ye; Panpan Shi; Huiyu Li; Chang Liu; Lin Liu; et al. (Science China Life Sciences, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Arabidopsis MPK2 negatively regulates drought tolerance by balancing growth and stress responses - Yuzhen Li; Yi Feng; Na Li; Jisheng Li; Heng Zhou; Linfei Liu (Plant Science, 2026)

Human activities dominate the euphotic zone depth in Yunnan plateau lakes from Landsat observations (1986–2024) - Chao Huang; Yiming Yang; Yunmei Li; Xianzhang Dong; Yanhong Yu; Heng Lyu; Junda Li; Yuxin Zhu; Jianzhong Li; Wenyu Liu; Gaolun Wang; Mengmeng Song; et al. (Journal of Hydrology, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Fluid evolution and petroleum accumulation in the Middle Permian gas reservoirs of the Sichuan Basin, China - Yun Liao; Jianyong Zhang; Zeqi Li; Heng Wang; Juan Wu; Genshun Yao; Wenzheng Li; Feng Liang; Shugen Liu; Bin Deng (Journal of Asian Earth Sciences, 2026)

Enzyme-hydrolyzed polysaccharides from Morchella importuna: preparation, structural characterization, and multi-omics of lipid metabolism regulation - Dongjie Li; Heng Miao; Ruru Liu; Xu Pan; Yuting Pei; Guoqing Wei; Xueran Geng; Yanfen Cheng; Junlong Meng; Ludan Hou; Mingchang Chang; Lijing Xu (Food Chemistry, 2026)

Retarding fouling evolution in ultrafiltration via single-atom-catalyst-functionalized nanochannels: An in-depth exploration of foulant migration pathways - Junwen Ding; Shirong Li; Peijie Li; Zihan Liu; Jialin Song; Nan Yue; Daliang Xu; Langming Bai; Jiaxuan Yang; Heng Liang (Chemical Engineering Journal, 2026)

Impact of boundary layer schemes in RegCM-Chem on East Asian climate and its response to the aerosol-radiation interaction - Heng Cao; Bingliang Zhuang; Yinan Zhou; Peng Gao; Yaxin Hu; Tijian Wang; Shu Li; Mengmeng Li; Min Xie; Qian Liu (Atmospheric Research, 2026)

Mucor melanoleucus (Mucorales, Mucoromycota), A New Species Isolated from Ailuropoda melanoleuca (Giant Panda) Feces - Fei Li; Qing-Feng Zhou; Heng Zhao; Xiao-Yong Liu (Current Microbiology, 2026)

The influence of native temporal resolution on the performance of real-time global ionospheric maps - Hengyu Wang; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Li Yang; Chuanding Zhang; Germán Olivares-Pulido; Kualong Xu (GPS Solutions, 2026)

Urban forest canopies are both source and sink for Pb and Hg deposition in subtropical southern China - Cheng Li; Dongqing Ji; Jin Wang; Heng Jiang; Xinyu Jiang; Cao Hao; Xiaodong Liu; Xiangdong Li; Jiong Cheng (Urban Forestry & Urban Greening, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Metabolomic and transcriptomic analysis reveals the impact of fruit bagging on cork spot disorder in ‘Akizuki’ pear fruit - Xueqian Wang; Lingxia Chen; Zixiao Wu; Jie Deng; Jintong Hu; Wei Wu; Bing Jia; Lun Liu; Xiaomei Tang; Li Liu; Zhenfeng Ye; Wei Heng (Postharvest Biology and Technology, 2026)

Soil-associated microorganisms: A natural source of biologically active compounds - Nigora Rustamova; Jakhongir Movlanov; Dildora Alimova; Heng Yin; Guozheng Huang; Maksud Isokov; Tang Li; Nasiba Khodjaeva; Aktam Nurniyozov; Sobirdjan Sasmakov; Batyr Khasanov; Dilmurod Murodullayev; et al. (Phytochemistry, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Redox control on protodolomite formation in post-extinction microbialites: evidence from the Permian‒Triassic boundary beds in South China - Danna Liu; Pieter T. Visscher; Yuangeng Huang; Qian Fang; Yu Pei; Zi-Heng Li; Zijie Zheng; Zhong-Qiang Chen (Geochimica et Cosmochimica Acta, 2026)

Experimental and theoretical study on the ultimate bearing capacity of U-shaped steel-concrete composite cap beams - Heng Liu; Lin Xiao; Xing Wei; Xiang Li; Jian Ren; Huijun Wang (Engineering Structures, 2026)

Ultra-stable targeted P-modified carbon-encapsulated Pt catalyst enables electronic recognition for efficient synthesis of p-aminophenol from nitrobenzene - Yebin Zhou; Wanzhe Zhou; Fang Huang; Yu Liu; Xiaofeng Zhu; Kaijun Jiang; Chunyu Yin; Xiaohua Wang; Heng Huang; Chaofan Ma; Yangzhen Jin; Qunfeng Zhang; et al. (Chemical Engineering Journal, 2026)

EGR1 regulates degranulation and mediator release in C48/80-induced pseudo-allergic reactions - YiZhao Sun; Heng Li; Juntao Li; YaoJun Wang; Tongyun Long; Zhe Cui; Yanfen Zhang; Zhongcheng Liu (Immunologic Research, 2026)

Effects of Excessive Manganese Exposure on Testicular Oxidative Stress, Histopathology, and Nrf2 Signaling Pathway in Mice - Dianyi Peng; Fuqing Feng; Heng Yin; Jianfei Zhao; Shanchuan Cao; Li Zhang; Jingbo Liu (Biological Trace Element Research, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

A self-sustained and self-sensing ocean observation buoy: System integration and in-situ sea trial - Yunfei Li; Tianyi Tang; Heng Zhao; Lining Sun; Fusheng Zha; Huicong Liu (Ocean Engineering, 2026)

Ecotoxicity of silver nanoparticles in marine waters: Global gap between exposure and seawater quality criteria - Qing-Wei Li; Heng Zhang; Xin-Ming Pu; Daosen Liu; Jin Li; Romana Manzoor; Jin-Fen Pan (Marine Environmental Research, 2026)

Effects of pig bone‑derived hydroxyapatite on contaminated manure composting: Humification, copper/zinc immobilization, and high‑risk antibiotic resistance genes - Jiaxin Liu; Chaoqun Yan; Shulin Zhang; Guoquan Zeng; Shiyu Ma; Jingtong Dai; Huayan Huang; Yanglong Li; Feifan Yu; Yu-xian Shangguan; Heng Xu; Huakang Liu (Journal of Hazardous Materials, 2026)

Speciation-dependent bioaccessibility of lead in e-waste dismantling soils: Synchrotron spectroscopy reveals molecular controls across physiological compartments - Jian Liu; Yi-Fan Li; Yi-Heng Wang; Dong-Xing Guan; Hao-Ran Guan; Yi-Ren Li; Xing-Mei Liu (Journal of Hazardous Materials, 2026)

Remote sensing image dehazing: A systematic review of progress, challenges, and prospects - Heng Zhou; Xiaoxiong Liu; Zhenxi Zhang; Jieheng Yun; Chengyang Li; Yunchu Yang; Dongyi Xia; Chunna Tian; Xiao-Jun Wu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Duration of high temperature-pressure conditions in impact-induced plumes on the Moon - Xiaoying Liu; Chi Zhang; Zongyu Yue; Lixin Gu; Jing Li; Heng-Ci Tian; Sen Hu; Yangting Lin (Icarus, 2026)

Hotspots & trends of lactic acid bacteria fermentation characteristics: A bibliometric analysis - Xudong Zhao; Kaiyue Wang; Xinqi Wang; Wei Liu; Jia Li; Zhaojun Ban; Xingqian Ye; Heng Xu; Xiaoyu Wang; Yimiti Baharrguli; Longying Pei; Xujie Hou (Food and Humanity, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

A modelling study of orbital-scale precipitation variability and oxygen isotope evolution over arid Central Asia - Jing Lei; Zhengguo Shi; Heng Liu; Yingying Sha; Xinzhou Li (Science China Earth Sciences, 2026)

Nitrogen and phosphorus fertilisation suppresses litter mineralisation but sustains positive priming in semi-arid agricultural soil - Yuhuai Liu; Heng Wang; Xiantao Ai; Olga Shibistova; Tida Ge; Yongfu Li; Georg Guggenberger (Plant and Soil, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Four decades of terrestrial dissolved organic matter in lakes across the Yangtze River Delta: Spatiotemporal dynamics and driving factors - Song Miao; Heng Lyu; Huaiqing Liu; Yuan Li; Xiaoguang Ruan; Wenyu Liu (Journal of Hydrology, 2026)

Dual-functional NiCo2O4 nanofibers/chitosan aerogel for efficient solar evaporation and bacterial removal - Yuangao Li; Shan Chen; Rengfeng Luo; Liyan Xue; Heng Chen; Fengzhi Tan; Minzhong Huang; Zhaoli Liu; Fan Yang (Journal of Environmental Chemical Engineering, 2026)

Flavor enhancement of corn oil through the solid-state complex-enzyme hydrolysis: Process optimization and mechanistic insights - Guohao Sun; Shangde Sun; Yulan Liu; Hao Zhang; Yuxiang Ma; Yaoyao Zhang; Heng Du; Talha Ashfaq; Xuze Zhang; Zisong Li; Aiyue Wang (Food Chemistry, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Fructan PKP-1b from Polygonatum kingianum attenuates aging and neurodegeneration by inhibiting insulin/IGF-1 signaling - Haitao Guo; Jiahui Wang; Yueying Yuan; Jinchai Qi; Shuqi Li; Heng Chen; Zhixing Huang; Hao Liu; Shaojun Yu; Zekun Yu; Gengyang Liu; Jing Han; et al. (Carbohydrate Polymers, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Identification of the methionine sulfoxide reductase (MSR) gene family in four Triticum species and functional analysis of TaMSRB5 involved in copper stress tolerance in Arabidopsis thaliana - Heng Chen; Luzhen Wang; Kexin Zhao; Shuai Yan; Yifei Chen; Lei Guo; Yinying Wu; Renmei Tian; Danping Li; Wenjia Zhang; Jianjun Liu; Haosheng Li; et al. (Plant Molecular Biology, 2026)

Downregulation of SLC12A5 in glioblastoma multiforme: a novel prognostic biomarker associated with brain edema and radiomic features - Rongde Zhong; Zengwei Kou; Heng Wang; Qian Li; Yue Xiao; Zongyang Li; Weilin Chen; Fanfan Chen; Guodong Huang; Yunsheng Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

IonoMoni: ionospheric monitoring based on dual-frequency data from single GNSS station - Yuzhi Zhang; Yihong Zhang; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Chenxiang Wang; Chuanding Zhang; Li Yang; Huiling Yu; Wenkai Meng (GPS Solutions, 2026)

Expression of PSTPIP1 in Renal Cell Carcinoma and Its Prognostic Value - Yiyang Chen; Xiaowen Qin; Li Sun; Pu Zhang; Zhenghong Liu; Bin Zheng; Yixuan Mou; Haichang Li; Heng Wang; Dahong Zhang (Biochemical Genetics, 2026)

A novel method of estimating phytoplankton absorption coefficient for inland waters based on OLCI using Sun-induced chlorophyll-a fluorescence - Wenyu Liu; Yiling Zheng; Jie Lin; Yunmei Li; Honglei Guo; Huaiqing Liu; Yuxin Zhu; Fangfang Chen; Heng Lü; Song Miao (Journal of Oceanology and Limnology, 2026)

The Coupling Mechanisms of Alkalinity–Salinity–Soil Inorganic Carbon in Saline–Alkali Soils along the Yellow River - Hongfang Li; Hu Liu; Fu Heng; Hui Zhou; Qi Wang; Jian Wang (Journal of Soil Science and Plant Nutrition, 2026)

Macrophage RNA polymerase II subunit 5-mediating protein deficiency exacerbates kidney inflammation and fibrosis - Jiayi Nie; Benquan Liu; Heng Xiong; Ying Gao; Shuiying Li; Shuangquan Chen; Wenqiang Yu; Hua Liang (Inflammation Research, 2026)

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Angelicin attenuates sepsis-associated splenic injury by targeting NF-κB/JAK2/STAT3 and PI3K/Akt pathways to inhibit inflammation and apoptosis - Enzhuang Pan; Huilin Sun; Zhihao Ma; Shasha Zhang; Yedan Liu; Zihan Xu; Yusa Li; Xiaomin Jin; Heng Wang; Jingquan Dong (Toxicology and Applied Pharmacology, 2026)

Simultaneous removal of Cr(VI) and phosphate by a novel Bacillus tropicus strain PCr-6: The role of phosphate in the enhancement of Cr(VI) reduction - Dinghua Peng; Yanglong Li; Jiaxin Liu; Shizhong Zhang; Heng Xu (Environmental Research, 2026)

Hierarchical porous amorphous silica additive for long-life aqueous zinc-ion batteries - Shanshan Chen; Guorong Liu; Long Chen; Xun Lv; Jiayi Li; Heng Zhang; Xiong Li; Qing Wang; Jian Wang; Haojun Zhang; Shengchao Yang (Chemical Engineering Journal, 2026)

High-performance PAN/LiCl nanofiber membranes for respiratory protection against coal mine dust: Experimental validation and numerical simulation - Wen Nie; Meiyang Liao; Huitian Peng; Lidian Guo; Yunshuo Shi; Jinkun Zhang; Heng Liu; Mingyuan Lu; Yuhang Li; Xingchao Cha; Yanmei Zhao; Yunfei Nie (Building and Environment, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Marine heatwaves drive phytoplankton community shifts and chlorophyll a decline in the Bay of Bengal - Zhihao Yang; Pei Jiang; Yang Liu; Lin Deng; Zhimin Bai; Tuwang Li; Yuchen Liang; Zhongbing Chang; Heng Liu; Jun Zhao (Acta Oceanologica Sinica, 2026)

Microplastics pollution in aquaculture areas and the synergistic effects with antibiotics and heavy metals: A case study in Zhoushan, China - Yiyang Duan; Hongying Gao; Yaqian Liu; Hao Chang; Jianbo Yan; Yuchao Wang; Zhichao Zhang; Chengji Chen; Xueyan Li; Heng Wang; Heqing Shen (Regional Studies in Marine Science, 2026)

Petrogenesis of early Paleozoic mafic rocks in the North Qaidam, NW China: Evidence for lithosphere–asthenosphere interaction in continental arc–back-arc settings - Lei Wang; Manlan Niu; Xiucai Li; Chen Li; Zhen Yan; Hang Liu; Zhe Heng; Taichang Zhu (Lithos, 2026)

Study on the spatiotemporal changes of nutrients input in a plateau lake and its impact on the nutrient status—A case study of Dianchi lake - Gaolun Wang; Yunmei Li; Junda Li; Xianzhang Dong; Jianzhong Li; Heng Lyu; Yanhong Yu; Yuxin Zhu; Wenyu Liu (Journal of Hydrology, 2026)

Advancements in environmental microplastic removal and upcycling techniques - Tianyu Lin; Penggang Li; Huaping Jia; Heng Jiang; Fengjia Xie; Yanting Liu; James Kar-Hei Fang; Changchao Li; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

Building an efficient simultaneous aerobic nitrification and denitrification (SAND) system by enhancing interspecies electron transfer (IET) - Ke Li; Zhanqiu Liu; Xueliang Shao; Chaojie Li; Weiwei Lu; Qiaochu Liang; Huixia Lan; Heng Zhang; Yang Zhang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Design and synthesis of 2-amino-4-(trifluoromethyl)pyrimidine derivatives as potential Werner-dependent antiproliferative agents - Chang You; Shijiao Wei; Jia Yu; Guangcan Xu; Huimin Li; Xinyu Liu; Menghan Wang; Xueling Meng; Youyin Xu; Gang Yu; Heng Luo; Bixue Xu (Molecular Diversity, 2026)

Monitoring and prediction of ionospheric spatial gradients from global ionosphere maps: a comparative analysis - Kualong Xu; Qi Liu; Enric Monte-Moreno; Heng Yang; Manuel Hernández-Pajares; Germán Olivares‐Pulido; Li Yang; Chuanding Zhang (GPS Solutions, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Wenzhouxiangella psychrophila sp. nov., Wenzhouxiangella indolica sp. nov., and Halotectona sediminis gen. nov., sp.nov., three novel taxa with ability of IAA production from saline lake sediment - Qing-Yu Xu; Tayyiba Habib; Lei Gao; Dildar Wu; Xin-Yao Li; Thi-Nhan Khieu; Yue-Heng Chen; Yao Zhang; Yong-Hong Liu; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Systematic and Applied Microbiology, 2026)

Regulation of soil physical environment and erosion characteristics of farmland by amendments in the black soil region of Northeast China - Xu Leng; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Dong Liu; Zhaoqiang Zhou; Di Wu (Soil and Tillage Research, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

All-weather adaptive water-electricity cogeneration enabled by a wooden evaporator - Wang Lu; Yanpeng Cheng; Xinyuan Liu; Zhuoxun Liao; Shi Shuai; Heng Wang; Mengyuan Liu; Siqi Huan; Zhiguo Li; Yang Liu (Chemical Engineering Journal, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Precise molecular spacer engineering for tumor-responsive pKa tuning: a pan-cancer imaging platform for evaluating tumor microenvironment reprogramming capability - Hong Zhang; Fei-Fan Xiang; Ding-Heng Zhou; Yan-Hong Liu; Zhou-Yu Wang; Shan-Yong Chen; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Metal–phenolic networks improve biocontrol effect of Bacillus velezensis DM14 against pear anthracnose - Jianfeng Du; Heng Li; Shenjie Liu; Jiawei Tang; Xin Zhao; Yiming Liu; Limin Wu; Yue Li; Qixiong Gao; Fuxin Sun; Ninghai Lu; Xueliang Tian; et al. (Pesticide Biochemistry and Physiology, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

A molecular imprinting-switchable laccase-like nanozyme-based onsite self-calibrating assay of ethyl carbamate residues - Heng Wang; Cancan Jia; Siyu Huang; Sha Li; Xin Liu; Wenjuan Chen; Yizhong Shen (Food Chemistry, 2025)

Metabolic fate of polyphenols in LAB-fermented kiwifruit juice: A comparative study of single and mixed cultures with targeted metabolomics and enzymatic evidence - Heng Liu; Weichong Fu; Xinyue Lian; Chengwei Pu; Xinxin Wu; Jingming Li (Food Chemistry, 2025)

Synergistic enhancement of CO2 adsorption on Cu2(OH)PO4 via iron doping and polyethylenimine loading - Deqiang Zhao; Heng Lu; Qi Huang; Qiuhong Li; Siru Li; Yi Liu; Bojie Yuan (Environmental Research, 2025)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Population Genetics Study of Saccostrea malabonensis (Bivalvia: Ostreidae) in Hainan Island - Dansheng Xie; Fengping Li; Mingjie Liu; Xin Heng; Likai Fan; Xingchen Guo; Qingqiu Dong; Qianying An; Aimin Wang; Chunsheng Liu; Yi Yang (Journal of Ocean University of China, 2025)

Domain Adaptation with Deep Feature Clustering for Pseudo-Label Denoising in Heterogeneous SAR Image Classification - Sheng-Jie Luo; Zhi-Gang Liu; Xi-Hai Li; Yi-Ting Wang; Xiao-Niu Zeng; Zhi-Hao Zheng; Heng Li (Applied Geophysics, 2025)

Biomineralization-driven simultaneous carbon/phosphorus recovery and membrane fouling control in anaerobic membrane bioreactor for swine wastewater treatment - Qianyi Liu; Hongyu Xie; Yin Xu; Ziang Zhou; Yuqi Chen; Lan Lin; Rasheed Adeleke; Heng Li; Yuanpeng Wang; Shaohua Chen; Yanlong Zhang (Water Research, 2025)

Plastispheres as unique niches for promoting turnover of dissolved organic matter in aquatic environments - Yan-Jun Liu; Zheng-Hao Li; Yan-Yun Hu; Jia-Heng Zhao; Li Yuan; Guo-Ping Sheng (Water Research, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Ribosomal protein L22 and ribosomal protein L32 respond to Bacillus velezensis 1 stress through interactions - Heng Zhou; Wenxin Cao; Qiqi Zhang; Fangfang Liu; Yao Li; Yingxiu Wan (Pesticide Biochemistry and Physiology, 2025)

Improved unscented transformation method and its application in ship uncertainty-based optimization - Heng Li; Zuyuan Liu; Baiwei Feng; Qiang Zheng; Xiao Wei (Ocean Engineering, 2025)

Evaluating impacts of hydrology and pollution loadings on low dissolved oxygen in an urbanized tidal river network using modeling and monitoring - Heng Zhang; Jiahuan Liu; Tong Li; Siyu Zhang; Zhongyuan Lin; Zhengbo Jia; Wenping Gong; Guang Zhang (Journal of Hydrology, 2025)

Dynamic changes in composition during processing of Lonicerae japonicae flos black tea - Shuang Liu; Hongjing Dong; Heng Lu; Yufei Li; Guanhua Zhang; Yuzhang Mi; Xiao Wang (Food Chemistry, 2025)

How to achieve sodium salt reduction in bean-based fermented foods: strategies, application cases and future perspectives - Chengtuo Niu; Ying Liu; Heng Li; Chunfeng Liu; Jinjing Wang; Feiyun Zheng; Qi Li (Food Chemistry, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Effects of copper and zinc on three stages-anaerobic fermentation of organic wastes - Yingying Cai; Minhua Cheng; Xinxin Liu; Guangfei Qu; Hongmei Zou; Heng Li; Shiqiang Zhao; Nanqi Ren (Environmental Research, 2025)

Aquaculture types drive variability in mangrove soil carbon-nitrogen stocks and OC sources via dredging wastewater - Jiajia Wu; Liyue Liu; Hanyi Li; Jiahui Chen; Guangcheng Chen; Heng Zhu; Jun Liu; Yong Ye (Environmental Pollution, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Designing interfacial edge microenvironments of cobalt phosphide quantum dots/graphitic carbon nitride to modulate electron delocalization for ultrafast photocatalytic hydrogen evolution - Xiukun Hu; Yunxiong Zeng; Heng Liu; Bo Da; Hao Li; Bo Hong; Xiaoling Peng; Xinqing Wang (Chemical Engineering Journal, 2025)

Vertical distribution and migration mechanism of artificial radionuclides in Zhalong Wetland and Lake Chagan of the Nenjiang river basin - Chunping Huang; Yongjing Guan; Peijun Zhang; Deyu Wang; RanRan Li; Heng Li; Zhiyong Liu (CATENA, 2025)

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

Urbanization and ecosystem services: A spatiotemporal exploration in the Sichuan Portion of the Yellow River Basin - Xilong Zhu; Xiaoai Dai; Chao Liu; Ruihua Nie; Hongji Zhang; Qingsong Chen; Naiwen Li; Lei Ma; Ke Lu; Heng Lu (Journal of Mountain Science, 2025)

Water oxidation catalysts from electrochemical intercalating [PW12O40]3‐ and synthesizing layered double hydroxide on high conductivity rGO@Ni foam - Xiaoyan Zhu; Zhipeng Sun; Minghe Du; Yi Liu; Huixi Li; Heng Deng; Chunjie Yan; Shengping Wang (Applied Clay Science, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Nonradical-dominated nanoconfined iron single-atom catalytic membrane to enhance peroxymonosulfate activation for efficient water decontamination - Peijie Li; Daliang Xu; Xiaoxiang Cheng; Peng Liu; Xinsheng Luo; Jiaxuan Yang; Heng Liang (Water Research, 2025)

Polyethylene microplastics interfere with MICP-based cadmium remediation: A dual-system evaluation of microbial performance and environmental response - Huayan Huang; Maohang Jia; Dinghua Peng; Yumei Zhang; Xin Zheng; Yanglong Li; Shuang Feng; Jiaxin Liu; Heng Xu; Huakang Liu (Journal of Hazardous Materials, 2025)

Analysis of spatiotemporal changes and driving factors of green and blue carbon stocks in Zhangzhou City based on PLUS and InVEST models - Xiaoai Dai; Danlan Li; Yumeng Zheng; Chao Liu; Naiwen Li; Heng Lu (Journal of Cleaner Production, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Low-cost municipal solid waste incineration fly ash adsorbents for phosphate recovery: A potential green treatment process - Qianyi Liu; Jingjing Sun; Xuefeng Liu; Yan Li; Chengcheng Shen; Samir I. Gadow; Heng Li; Yanlong Zhang (Journal of Environmental Chemical Engineering, 2025)

Investigation of chlorate formation during agar extraction from Gracilaria: Process kinetics, thermodynamics, and mechanistic insights - Heng Li; Xiaohui Liu; Shuyu Zhang; Hui Ni (Food Bioscience, 2025)

Adaptive mechanisms of moss (Campylopus schmidii) to Cr(Ⅵ) stress in pyrite-mining polluted ecosystems: Integrating biochemical, structural, and molecular perspectives - Huayan Huang; Xin Zheng; Shan Tao; Shiyu Ma; Shuang Feng; Yanglong Li; Ke Liang; Guorui Li; Jia Lei; Huakang Liu; Heng Xu (Environmental Pollution, 2025)

Two birds with one stone: S-scheme charge transfer enables simultaneous efficient photocatalytic complete methanation of CO2 and benzimidazole synthesis - Wei Liu; Heng Zhang; Zhe Zhang; Yali Ji; Tiantian Xu; Xusheng Li; Jiao Chen; Mengyao She; Ping Liu; Shengyong Zhang; Jian-Li Li (Chemical Engineering Journal, 2025)

Synergistic regulation of plant growth regulators on somatic embryogenesis and optimization of rejuvenation culture in Sinocrassula indica (Decne.) Berger - Li-qing Cheng; Shuang Liu; Heng-yu Huang; Ai-li Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Agricultural SDHIs Induce Azole Resistance in Aspergillus fumigatus via Mitochondrial Sdh1 Suppression - Heng Zhang; Zhangling Zhu; Mengqi Peng; Sijie Liu; Xiao Gong; Tian Chen; Qingwen Hu; Linyun Li; Zha-xi Dun-zhu; Lha-zom Drol-ga; Yi Sun (Mycopathologia, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Investigation of CO2 absorption and desorption performance of DETA-based phase-change solvents in alcohol-water systems - Yining Wang; Chikezie Nwaoha; Teerawat Sema; Bin Liu; Zhiwu Liang; Paitoon Tontiwachwuthikul; Jin-Heng Li (Chemical Engineering Journal, 2025)

Photoinduced spectral narrowing in perovskite/organic heterostructures for high-selectivity near-infrared detection - Yu Zhang; Yaoyao Li; Heng Liu; Xiaowei Li; Ying Xu; Ziqi Zhu; Zhiqin Liang; Bo Qiao; Dandan Song; Swelm Wageh; Guangcai Yuan; Zheng Xu; et al. (Chemical Engineering Journal, 2025)

New perspectives on the removal of 17β-Estradiol using biochar-immobilized microbial agents: Driving role of quorum sensing in abundant species - Jiaxin Liu; Keke Wang; Jingtong Dai; Yuyuan Ouyang; Chaoqun Yan; Shulin Zhang; Yanglong Li; Huakang Liu; Heng Xu (Chemical Engineering Journal, 2025)

PdSe2/WS2/PdSe2 unipolar barrier photodetector for visible-infrared polarization detection, synaptic plasticity simulation and neuromorphic visual system - Wenhao Fan; Hui Yan; Heng Li; Xinjian Liu; Yu Zhang; Weijie Bai; Mengyang Li; Yanxia Li; Jin Zhang; Jiayu Zhao; Shishuai Sun; Qingguo Wang; et al. (Chemical Engineering Journal, 2025)

Coupling covalent organic framework with polyacrylamide to construct a robust composite hydrogel electrolyte for dendrite-free and long-lifespan aqueous zinc-ion batteries - Ziming Liu; Xiangcai Li; Heng Zhang; Xuke Zhang; Junyuan Li; Yifei Shi; Dongxiang Geng; Zhaolei Li; Dawei Sha; Genxi Yu; Chao Yan (Chemical Engineering Journal, 2025)

Genetic mapping and isolation of Rht28, a locus on wheat chromosome arm 2AL affecting plant height, grain size, and grain weight - Zhuo Liu; Jiaojiao Zhu; Qiuyue Zhao; Yiwen Cao; Qiuhong Wu; Junru Zhang; Yongxing Chen; Qingpeng Sun; Runzhi Li; Heng Tang; Zhiyong Liu; Jun Han (Theoretical and Applied Genetics, 2025)

Longitudinal relationships between changes in post-COVID mental fatigue and neuropsychiatric symptoms across distinct recovery trajectories - Wenrui Bao; Siyuan Chen; Ningkun Hong; Gengchen Ye; Chiyin Li; Jingmei Xie; Peng Li; Heng Li; Yang Wang; Jixin Liu; Xuan Niu; Yuchen Zhang (Inflammopharmacology, 2025)

An approach for mapping phytoplankton communities in freshwater lakes based on phytoplankton absorption features - Yuxin Zhu; Qingxia Miao; Heng Lyu; Yiling Zheng; Wenyu Liu; Yunmei Li; Junda Li; Fangfang Chen; Song Miao (Water Research, 2025)

Longitudinal transport of net suspended sediment in the river-dominated Modaomen Estuary of the Pearl River: Effects of river, tide, and mouth bar - Xinran Li; Feng Liu; Hao Zou; Chao Tan; Jie Huang; Sihao Mo; Haiwei Li; Rongyao Xie; Heng Wang (Marine Geology, 2025)

Prenatal exposure to PM2.5 constituents and newborn leukocyte telomere length in a prospective study: Windows of susceptibility and modification by maternal folic acid supplementation - Gaojie Fan; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Chao Xiong; Zhongqiang Cao; et al. (Journal of Hazardous Materials, 2025)

Mesoporous heterostructure SiO2@SiC@C composites for enhanced electromagnetic wave absorption - Xiaowei Zhang; Heng Lu; Bowen Gao; Shijie Li; Jiawei Wang; Bo Zhong; Chunli Guo; Yanqing Yang; Yuan Liu; Weike Zhang (Chemical Engineering Journal, 2025)

Intelligent Suppression of Marine Seismic Multiples Using Deep Learning Methods - Guang Hu; Yan Li; Shengxiong Yang; Heng Zhang; Xin Liu; Yuanheng Li; Dongmei Tian (Journal of Ocean University of China, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

Continental melting and growth through subduction processes: Evidence from the petrogenesis of Paleozoic granitoids and gabbros in the Qinling Orogen - Zhi-Wei Fan; Bin Li; Yong-Jun Shao; Matthew J. Brzozowski; John A. Mavrogenes; Yi-Qu Xiong; Ji-Heng Su; Qing-Quan Liu (Lithos, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Microbial behavior drives structure and composition changes during bio-cake evolution and implications for membrane fouling mitigation - Yazhou Sun; Zedong Lu; Chaoran Liu; Xing Li; Zhiwei Zhou; Jiawei Ren; Chen Li; Heng Liang (Chemical Engineering Journal, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Archean to early Mesoproterozoic crustal evolution of the Yangtze Craton: Insights from U-Pb-Hf-O isotopic and trace elemental compositions of detrital zircon - Xinyu Cai; Rui Li; Guangyan Zhou; Heng Luo; Zhifu Liu; Nimat Ullah Khattak; Wei Wang (Precambrian Research, 2025)

Enhanced tetracycline degradation through electron transfer activated by Bacillus cereus synthesized bio-FeS nanoparticles - Huixia Lan; Ke Li; Qiliang Cao; Zhanqiu Liu; Qiaochu Liang; Binghua Yan; Jiuqing Liu; Heng Zhang; Yang Zhang (Journal of Hazardous Materials, 2025)

Exposure to green space and leukocyte mitochondrial DNA copy number in children and adolescents - Gaojie Fan; Xiaoning Lei; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Jing Wei; et al. (Environmental Research, 2025)

Texture-Based Segmentation of SEM Images of Shale Rocks and Estimation of Meso-Scale Elastic Modulus by 2D FEM - Chunxiao Li; Yansong Liu; Longsheng Li; Zihang Wang; Heng Li (Rock Mechanics and Rock Engineering, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Experimental and numerical investigation on the superheated and subcooled ammonia spray characteristics under high injection pressure - Rui Yang; Heng Liu; Bing Li; Qinglong Tang; Mingfa Yao (Fuel, 2025)

Antiscalant-free strategy for nanofiltration: Prolonged induction period of gypsum crystallization at ultralow pressure - Longfeng Hu; Zihan Liu; Jinjin Jia; Nuo Cheng; Shu Jiang; Hesong Wang; Jiaxuan Yang; Jinlong Wang; Guibai Li; Heng Liang (Desalination, 2025)

PdRh bimetallic-loaded α-Fe2O3 nanospindles with Ppb-limit of 3-hydroxy-2-butanone biomarker detection: Particle dimension regulation and oxygen spillover effect - Xing-Yu Wang; Ping-Ping Liu; Hai-Jie Cai; Miao-Miao Li; Chun-Hui Deng; Yong Zhao; Zhao-Huan Zhang; Yong-Heng Zhu (Chemical Engineering Journal, 2025)

EBMGP: a deep learning model for genomic prediction based on Elastic Net feature selection and bidirectional encoder representations from transformer's embedding and multi-head attention pooling - Lu Ji; Wei Hou; Heng Zhou; Liwen Xiong; Chunhai Liu; Zheming Yuan; Lanzhi Li (Theoretical and Applied Genetics, 2025)

Association between multiple metals mixture and diabetic retinopathy in older adults with diabetes mellitus: a cross-sectional study in China - Shuren Ding; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Zhiqiang Zhao; Qing Wei; Shurong Pi; Fubin Chen; Qian Gu; Baixiang Xiao; et al. (Environmental Geochemistry and Health, 2025)

Moisture–Microbial Interaction Amplifies N 2 O Emission Hot Moments Under Deepened Snow in Grasslands - Jie Luo; Yong Peng; Zhou Jia; Yuntao Wu; Yuxuan Gao; Nairsag Jalaid; Xingming Zhang; Heng Ge; Bowen Qing; Hongyi Chen; Yanxin Zhan; Ping Li; et al. (Global Change Biology, 2025)
Freeze–thaw‐induced N 2 O pulses could account for nearly half of annual N 2 O fluxes in cold climates, but their episodic nature, sensitivity to snow cover dynamics, and the challenges of cold‐season monitoring complicate their accurate estimation and representation in global models. To address these challenges, we combined in situ automated high‐frequency flux measurements with cross‐ecoregion soil core incubations to investigate the mechanisms driving freeze–thaw‐induced N 2 O emissions. We found that deepened snow significantly amplified freeze–thaw N 2 O pulses, with these ~50‐day episodes contributing over 50% of annual fluxes. Additionally, freeze–thaw‐induced N 2 O pulses exhibited significant spatial heterogeneity, ranging from 3.4 to 1184.1 μg N m −2 h −1 depending on site conditions. Despite significant spatiotemporal variation, our results indicated that 68%–86% of this variation can be explained by shifts in controlling factors: from water‐filled pore space (WFPS), which drove anaerobic conditions, to microbial constraints as snow depth increases. Below 43% WFPS, soil moisture was the overwhelmingly dominant driver of emissions; between 43% and 66% WFPS, moisture and microbial attributes (including denitrifying gene abundance, nitrogen enzyme kinetics, and microbial biomass) jointly triggered N 2 O emissions pulses; above 66% WFPS, microbial attributes, particularly nitrogen enzyme kinetics, prevailed. These findings suggested that maintaining higher soil moisture served as a trigger for activating microbial activity, particularly enhancing nitrogen cycling. Furthermore, we showed that hotspots of freeze–thaw‐induced N 2 O emissions were linked to high root production and microbial activity in cold and humid grasslands. Overall, our study highlighted the hierarchical control of WFPS and microbial processes in driving freeze–thaw‐induced N 2 O emission pulses. The easily measurable WFPS and microbial attributes predictable from plant and soil properties could forecast the magnitude and spatial distribution of N 2 O emission “hot moments” under changing climate. Integrating these hot moments, particularly the dynamics of WFPS, into process‐based models could refine N 2 O emission modeling and enhance the accuracy of global N 2 O budget prediction.

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Regulating gypsum scaling-induced wetting in membrane distillation by heterogeneous crystallization: Role of filter media - Haiqing Chang; Zeren Ma; Huaxin Zhao; Dan Qu; Caihong Liu; Zhongsen Yan; Rui Li; Fangshu Qu; Heng Liang; Radisav D. Vidic (Water Research, 2025)

Nanofiltration membranes with fast water transport induced by controlled interfacial diffusion to enhance desalination and micropollutant removal - Zihui Wang; Haiping Liu; Zihan Liu; Ying Wang; Jiaxuan Yang; Langming Bai; Jinlong Wang; Han Zhang; Guibai Li; Heng Liang (Water Research, 2025)

Thioketal-photocage: a universal modification strategy for constructing new photochemical tools for real-time imaging in living cells - Ding-Heng Zhou; Shan-Yong Chen; Yan-Zhao Liu; Hong Zhang; Jun-Mei Li; Qian Zhou; Fei-Fan Xiang; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Study on a novel hydraulic rotary wind-spray control combined dust reduction device for shearer - Wen Nie; Mingyuan Lu; Lidian Guo; Huitian Peng; Jiuchao Li; Ao Tang; Heng Liu; Jinkun Zhang (Process Safety and Environmental Protection, 2025)

Basing target enzyme study the enantioselective bioactivity action mechanism of flusulfinam, a novel HPPD inhibitor herbicide - Shiling Liu; Siying Qin; Tengfei Zhang; Heng Zhang; Junqi Zhu; Xiaoli Li; Yuanfu Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2025)

AUV maneuvering modeling using system identification methods with adaptive VMD, improved CNN, and free-running model test - Bin Mei; Chenyu Li; Dongdong Liu; Jie Zhang; Heng Wang (Ocean Engineering, 2025)

Synergistic effects of heat stress and mastitis induced by K. pneumoniae on inflammation responses and blood-milk barrier in rats - Jia Guo; Qinqin Cao; Zhihao Wang; Pengzi Wang; Kangjun Liu; Long Guo; Junsheng Dong; Luying Cui; Jianji Li; Guoqiang Zhu; Xia Meng; Heng Wang (Journal of Thermal Biology, 2025)

Nitrate nitrogen concentrations drive microbial community composition and functional responses in microplastic surface biofilms - Shuangshuang Li; Yu Zheng; Chun Wang; Duo Xu; Heng Liu; Yan Song (Journal of Environmental Chemical Engineering, 2025)

Study of the interaction between polysaccharides and liposomes based on low-field nuclear magnetic resonance - Tingting Zhang; Heng Yu; Chenping Li; Yanping Wang; Chenxi Zheng; Yingli Hu; Jianzhong Han; Jianhua Liu; Weilin Liu (Food Bioscience, 2025)

Chemically activating biomass into hierarchically porous carbon as an efficient sulfur host for high-performance room temperature Na-S batteries - Jiawang Liu; Heng Zhang; Baojian Xie; Junquan Cheng; Tao Song; Youcun Bai; Ruguang Ma; Chang Ming Li (Chemical Engineering Journal, 2025)

Ball milling-induced strain engineering in nanoporous catalysts for tailoring hydrogen evolution reaction - Qite Li; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Zhenduo Cui; Heng Liu; Shengli Zhu (Chemical Engineering Journal, 2025)

Spatiotemporal influence of driving factors on water conservation in underdeveloped plateau regions: a case in the Yellow River Basin of Sichuan, China - Xuan Wang; Lei Ma; Heng Lu; Chao Liu; Ruihua Nie; Naiwen Li; Xiao Tan; Zhengli Yang (Journal of Mountain Science, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

Role of Glucose Metabolism in the Effects of Serum Metals on Telomere Length: Findings in Chinese Diabetic Population - Shuren Ding; Qian Gu; Zhiqiang Zhao; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Qing Wei; Shurong Pi; Fubin Chen; Baixiang Xiao; et al. (Biological Trace Element Research, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Design and parameter optimization of air-delivery auxiliary seed guide for pneumatic plate precision rapeseed metering device - Zhaodong Li; Heng Zhang; Jialuo Huang; Chao Lou; Yongxin Chen; Lichao Liu; Tian Zhang; Liqing Chen (Computers and Electronics in Agriculture, 2025)

Soil water content prediction across seasons using random forest based on precipitation-related data - Pei-Yuan Chen; Chien-Chih Chen; Chu Kang; Jia-Wei Liu; Yi-Heng Li (Computers and Electronics in Agriculture, 2025)

Monitoring the circumferential cracking of inner concrete core in prestressed concrete cylinder pipe during wire-wrapping using distributed optical fiber sensors - Shuai Liu; Yanlong Li; Ye Zhang; Minghui Ma; Wen Qiu; Lei She; Heng Zhou; Kangping Li; Kaiyu Sun (Tunnelling and Underground Space Technology, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Satellite remote sensing of turbidity in Lake Xingkai using eight years of OLCI observations - Jian Li; Yang Li; Kaishan Song; Ge Liu; Shidi Shao; Bingqian Han; Yujin Zhou; Heng Lyu (Journal of Environmental Management, 2025)

Identification and differential expression analysis of microRNAs in the liver and spleen tissues of Yunnan Zebu and Holstein cattle - Rong Liu; Hesong Liu; Rong Li; Chunqing Li; Heng Xiao; Shanyuan Chen (Tropical Animal Health and Production, 2025)

Identification of EXO1 as a potential biomarker associated with prognosis and tumor immune microenvironment for specific human cancers - Jingyun Wang; Fen Liu; Jianfu Heng; Guoli Li (Mammalian Genome, 2025)

PbSQE3 and PbSQE6 regulates the formation of triterpenoid compounds in the russet mutant of ‘Dangshansuli variety’ pear - Zhenfeng Ye; Daozhi Yao; Qi Liu; Lingxia Chen; Lindong Dou; Jinhui Yu; Jie Deng; Zixiao Wu; Li Cao; Li Liu; Wei Heng (Acta Physiologiae Plantarum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Low-temperature oxidative pyrolysis characteristics of tobacco components - Zhongya Guo; Ke Zhang; Huanwei Li; Lili Fu; Qi Zhang; Ze Liu; Le Wang; Xueyi Qiao; Heng Guo; Ran Chen; Bing Wang; Bin Li (Biomass and Bioenergy, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

Global warming creates the adaptation tipping points of livestock exposure to cold and heat stress on the Qinghai-Tibetan plateau - Ning Zhan; Weihang Liu; Tao Ye; Yiqing Liu; Zitong Li; Heng Ma (Agricultural Systems, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Gestational exposure to carbon black nanoparticles triggered fetal growth restriction in mice: The mediation of inactivating autophagy-lysosomal degradation system in placental ferroptosis - Jing Li; Hongying Gao; Zehua Xu; Biling Gao; Liang Zhang; Bowen Su; Shijing Yang; Jiangling Liu; Ya Liu; Xiuxiu Wang; Heng Wang; Yi Lin; et al. (Science of The Total Environment, 2025)

Distinct ultrafast dynamics of bilayer and trilayer nickelate superconductors regarding the density-wave-like transitions - Yidian Li; Yantao Cao; Liangyang Liu; Pai Peng; Hao Lin; Cuiying Pei; Mingxin Zhang; Heng Wu; Xian Du; Wenxuan Zhao; Kaiyi Zhai; Xuefeng Zhang; et al. (Science Bulletin, 2025)

Enhancing butyrate synthesis and intestinal epithelial energy supply through mixed probiotic intervention in dextran sulfate sodium-induced colitis - Heng Zhang; Jingzhou Sun; Aowen Xie; Huiqin Yang; Yingjun Li; Yuxia Mei; Jinshan Li; Lei Xiao; Yangyang Liu; Yunxiang Liang (Food Bioscience, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Fabrication of green xylose-based nanofiltration membrane with enhanced performance and chlorine resistance - Yumeng Xie; Jing Ren; Peng Liu; Junfeng Zheng; Zhaohuan Mai; Yanyan Liu; Xuewu Zhu; Xin Li; Daliang Xu; Heng Liang (Desalination, 2025)

Inspired by the tessellation of strawberry achenes on skin: Preparation of ZIF-67 derived multifunctional flame retardant through supramolecular assembly of cobalt alginate biopolymer in melamine-containing polyphosphazene skeleton - Qianlong Li; Yu Lei; Xue Bi; Yina Liu; Ye-Tang Pan; Wei Wang; Wenchao Zhang; Congling Shi; Guan Heng Yeoh (Chemical Engineering Journal, 2025)

Spin-state regulation of heteronuclear Cu-Co dual-atomic sites via tuning electronic asymmetry for enhanced oxygen reduction - Heng Wang; Xinzhi Zhou; Jiaxin Su; Zixian Liu; Bingbing Xiao; Long Yang; Jun Wang; Yuanli Li; Xunyu Lu; Xiaofeng Zhu (Chemical Engineering Journal, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

UAV-Based Simulation of 3D Random Discontinuity Networks in Rock Slopes - Na Chen; Zhi-Wei Liu; Heng-Lin Xiao; Li-Hua Li (Geotechnical and Geological Engineering, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Aquibaculum sediminis sp. nov., a halotolerant bacteria isolated from salt lake sediment - Qing-Yu Xu; Lei Gao; Dildar Wu; Xin-Yao Li; Yong-Hong Liu; Yao Zhang; Yue-Heng Chen; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

More than a contaminant: How zinc promotes carbonate-mineralizing bacteria metabolism and adaptation by reshaping precipitation conditions - Shiyao Li; Yongyun Li; Yanbing Yang; Can Wang; Fei Xu; Dinghua Peng; Huayan Huang; Yong Guo; Heng Xu; Huakang Liu (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Comprehensive understanding the impacts of polyethylene microplastics (PE-MPs) on freshwater biofilms: Tracking from growth, microbial community structure to element metabolisms - Shuangshuang Li; Mingcan Cai; Yu Zheng; Duo Xu; Heng Liu; Yan Song; Chun Wang (Journal of Water Process Engineering, 2024)

Influence of S(IV) reduction on the reaction mechanisms and the generation of reactive oxygen species in B-Cu@Fe/PPS system - Xin Zhou; Yang Liu; Chuanshu He; Yuqi Zhang; Yujia Xiang; Jialong Yin; Shuai Yang; Zirong Li; Yue Yuan; Peng Zhou; Yi Ren; Heng Zhang; et al. (Journal of Hazardous Materials, 2024)

Catalytic membrane with dual-layer structure for ultrafast degradation of emerging contaminants in surface water treatment - Qieyuan Gao; Xinyao Jin; Xi Zhang; Junwei Li; Peng Liu; Peijie Li; Xinsheng Luo; Weijia Gong; Daliang Xu; Raf Dewil; Heng Liang; Bart Van der Bruggen (Journal of Hazardous Materials, 2024)

Critical role of soil-applied molybdenum dioxide composite biochar material in enhancing Cr(VI) remediation process: The driver of Fe(III)/Fe(II) redox cycle - Mingxuan Liu; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Ping Xue; Xuechen Yang; Mo Li; Dong Liu (Journal of Environmental Management, 2024)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Mid-Miocene (17–11 Ma) fast exhumation in the upper Jinsha River and its implication for regional faulting in Southeast Tibet - Xuwen Shen; Jing Liu-Zeng; Xiaoming Shen; Xianyang Zeng; Zijun Wang; Yukun Xing; Heng Wang; Mohan Li (Geomorphology, 2024)

Biochemical and chemosensory characterization of doubanjiang fermented via two-stage controlled temperature - Chengtuo Niu; Yiyang Liu; Heng Li; Chunfeng Liu; Qi Li (Food Chemistry, 2024)

CO2-responsive multifunctional label based on chitosan and hyaluronic acid for visualizing and maintaining postharvest freshness - Haiyu Du; Xinru Liu; Xiaoli Sun; Heng An; Yiyi Li; Zhu Zhu; Yongqiang Wen (Food Hydrocolloids, 2024)

Predicting plateau atmospheric ozone concentrations by a machine learning approach: A case study of a typical city on the southwestern plateau of China - Qiyao Wang; Huaying Liu; Yingjie Li; Wenjie Li; Donggou Sun; Heng Zhao; Cheng Tie; Jicang Gu; Qilin Zhao (Environmental Pollution, 2024)

Nature-inspired ultrathin wood-based interfacial solar steam generators for high-efficiency water purification - Min Li; Yating Sun; Yuzhang Lei; Gonggang Liu; Heng Jiang; Yong Wang; Shanshan Chang; Xianjun Li; Jinbo Hu (Desalination, 2024)

Gradient Mo1−xWxSe2 monolayer alloys: Synthesis and multifunctional applications - Weijie Bai; Hui Yan; Can Su; Yu Zhang; Heng Li; Wenhao Fan; Xinjian Liu; Sándor Kunsági-Máté; Qingguo Wang; Shougen Yin (Chemical Engineering Journal, 2024)

Dual activation of soybean resistance against Phytophthora sojae by pectin lyase and degraded pectin oligosaccharides - Guangzheng Sun; Yeqiang Xia; Kuikui Li; Qinsheng Zhu; Feifei Ding; Hui Gu; Zhichao Zhang; Xinrui Li; Xuan Mi; Jun Chen; Ruoting Yao; Sicong Zhang; et al. (Science China Life Sciences, 2024)

Exploring the initiating mechanism, monitoring equipment and warning indicators of gully-type debris flow for disaster reduction: a review - Yan Du; Hui Liu; Heng Li; Mowen Xie; Santos D. Chicas; Jidong Wu; Fuxia Lv; Yaxin Wu (Natural Hazards, 2024)

The role of TRPV4 in programmed cell deaths - Qingjie Ma; Jilin Wu; Huixian Li; Xiaoshu Ma; Renwan Yin; Liping Bai; Heng Tang; Na Liu (Molecular Biology Reports, 2024)

High-Precision Re-Os Geochronology of the newly Discovered Lihefu Deposit Reveals the ∼145 Ma Mo Mineralization in Daye District, Eastern China - Hao Hu; Longpeng Li; Heng Luo; Yi Huang; Fang Sun; Jinhua Liu; Xiaodong Deng (Journal of Earth Science, 2024)

Unpuzzling spatio-vertical and multi-media patterns of aniline accelerators/antioxidants in an urban estuary - Ruihe Jin; Bao Li; Yan Wu; Yue Li; Xinyu Du; Chunjie Xia; Heng Zhao; Min Liu (Water Research, 2024)

Nano-confined catalysis with Co nanoparticles-encapsulated carbon nanotubes for enhanced peroxymonosulfate oxidation in secondary effluent treatment: Water quality improvement and membrane fouling alleviation - Peijie Li; Daliang Xu; Yunfei Gao; Peng Liu; Zihan Liu; Junwen Ding; Junyong Zhu; Heng Liang (Water Research, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Spatiotemporal evolution and interaction of water constraints and their socio-ecological drivers in the Taihu Lake Basin - Gaoyuan Wang; Junnan Liu; Zilin Wang; Yang Xiang; Chye Kiang Heng; Xiaojiao Li (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Response of Northern Hemispheric climate and Asian monsoon to dust darkened snow cover changes during the Last Glacial Maximum - Liu Yang; Zhengguo Shi; Xiaoning Xie; Heng Zhang; Xinzhou Li (Atmospheric Research, 2024)

Effects of environment and human activities on rice planting suitability based on MaxEnt model - Saiji Heng; Na Li; Qiliang Yang; Jiaping Liang; Xiaogang Liu; Yazhou Wang (International Journal of Biometeorology, 2024)

Development of a streamlined framework for probabilistic and comparative life cycle assessment of road pavements - Haoran Li; Miaomiao Zhang; Heng Liu; Hessam AzariJafari; Randolph Kirchain (Resources, Conservation and Recycling, 2024)

Selective depression of galena in the galena and chalcopyrite system by the Fe(II)-activated persulfate process - Qinbo Cao; Yan Yan; Heng Zou; Haiyu Zhang; Dianwen Liu; Shuming Wen; Yanjun Li (Minerals Engineering, 2024)

Selective production of dihydroxyacetone and glyceric acid from glycerol photo-oxidation - Jiu Wang; Bo Liu; Zheng Li; Yejun Xiao; Heng Zhao; Liquan Jing; Na Zhong; Bei Li; Md Golam Kibria; Jinguang Hu (Chemical Engineering Journal, 2024)

In vitro cluster buds regeneration and control of shoot tip necrosis in tissue cultures of Trichosanthes cucumerina L. - Cheng-Li Liu; Jie-Mei Deng; Hong-Mei Yan; Heng-Yu Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Dynamic functional connectivity correlates of mental workload - Zhongming Xu; Jing Huang; Chuancai Liu; Qiankun Zhang; Heng Gu; Xiaoli Li; Zengru Di; Zheng Li (Cognitive Neurodynamics, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

The time-advance effect of China's rooftop solar photovoltaics program on the dual carbon targets and its implication on the globe - Hong-Wei Lu; Yi-Ming Yan; Dong-Zhe Liang; Xu Duan; Heng-Chen Li; Yun-Long Liu; Zhen-Jie Tang (Sustainable Cities and Society, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

Tunable magnetism and band structure in kagome materials RETi3Bi4 family with weak interlayer interactions - Jingwen Guo; Liqin Zhou; Jianyang Ding; Gexing Qu; Zhengtai Liu; Yu Du; Heng Zhang; Jiajun Li; Yiying Zhang; Fuwei Zhou; Wuyi Qi; Minghui Cui; et al. (Science Bulletin, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

A hyperstable, low-salt adapted protease from halophilic archaeon with potential applications in salt-fermented foods - Jing Hou; Qing-Ke Zhang; Ruo-Yao Zhang; Si-Ya Li; Yuan-Yiyi Liu; Heng-Lin Cui (Food Research International, 2024)

Sustainable water sterilization by nano-ZnO using anisotropic polysaccharide columns derived from agro-waste stalk - Xue Wu; Yulin Liu; Meng Li; Bowen Li; Xiaohui Mao; Qiankun Wang; Xiaoning Tang; Heng Zhang; Lincai Peng; Xin Gao (Chemical Engineering Journal, 2024)

Photo-enhanced precious metal recovery enabled by trithiocyanuric-linked covalent triazine frameworks - Huaimeng Li; Heng Zhang; Jiafang Liu; Zhenzhen Liu; Haimin Zhang; Guozhong Wang; Yunxia Zhang (Chemical Engineering Journal, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Oxidase-like nanozymes-driven colorimetric, fluorescence and electrochemiluminescence assays for pesticide residues - Sha Liu; Chao Nie; Fengjiao He; Guojian Wu; Heng Wang; Si Li; Chenxing Du; Zhi Zheng; Jieshun Cheng; Yizhong Shen; Jie Cheng (Trends in Food Science & Technology, 2024)

Study on Plant-blanket to reduce heavy metal migration caused by precipitation and to improve the soil environment of pyritic tailings - Kangkai Lin; Jiannan Jian; Yumei Zhang; Yikai Liu; Shiyao Li; Yun Zhao; Heng Xu (Science of The Total Environment, 2024)

A new species of Eirictis (Mammalia, Carnivora, Mustelidae) from Lower Pleistocene of Yuanmou Basin, Yunnan, China - Arya Farjand; Li-Ya Fu; Qi-Gao Jiangzuo; Zhi-Heng Liu; Jian Wang; Xin-Ying Zhou; Shun-Dong Bi; Li-Hua Wang (Palaeoworld, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

Bioelectrochemically altering microbial ecology in upflow anaerobic sludge blanket to enhance methanogenesis fed with high-sulfate methanolic wastewater - Yijing Gao; Shiliang Heng; Jiayi Wang; Zhaobin Liu; Yisheng Liu; Bin Chen; Yule Han; Wanjiang Li; Xueqin Lu; Guangyin Zhen (Bioresource Technology, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

Apoptosis and pyroptosis in the nasal mucosa of Syrian hamster during SARS-CoV-2 infection and reinfection - Heng Li; Xin Zhao; Xinglong Zhang; Huiwen Zheng; Yibin Wang; Jinghan Hou; Jing Li; Yurong Zhao; Shasha Peng; Yingyan Li; Xin Zhang; Yifan Zhang; et al. (Apoptosis, 2024)

Paleoenvironmental evolution and organic matter accumulation of the lower Cambrian Maidiping marine black shales in the intracratonic basin, western margin of Sichuan Basin, South China - Guodong Xia; Yuehao Ye; Shugen Liu; Heng Wang; Jinmin Song; Wei Sun; Bo Ran; Kun Jiao; Guoliang Xie; Bin Deng; Zhiwu Li; Yun Zeng (International Geology Review, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Mechanical Identification Method of Amplitude Warning False Alarm Points Based on Dynamical Time–Frequency Domain Analysis - Yan Du; Heng Li; Santos D. Chicas; Mowen Xie; Weikang Lu; Lize Ning; Jingnan Liu (Rock Mechanics and Rock Engineering, 2024)

Productivity in the Southern Ocean Antarctic Zone during the Northern Hemisphere Glaciation (NHG) and its link to atmospheric pCO2 - Yiming Wu; Jingteng Guo; Xiangyu Zhao; Wenshen Xiao; Heng Liu; Zhifang Xiong; Tiegang Li (Science China Earth Sciences, 2024)

Analysis of Root Response Mechanism of Quinoa Seedlings to Waterlogging Stress Based on Metabolome - Yirui Guo; Qianchao Wang; Heng Xie; Xuesong Zhang; Tingzhi Huang; Ping Zhang; Junna Liu; Li Li; Peng Qin (Journal of Plant Growth Regulation, 2024)

Effects of luteolin supplementation on growth, histology, antioxidant capacity, non−specific immunity and intestinal microbiota of the red swamp crayfish (Procambarus clarkii) - Yanbin Lin; Shengxuan Li; Yulong Li; Liu Fang; Heng Zhang; Qian Wang; Guoliang Ruan (Animal Feed Science and Technology, 2024)

High-valent metal-oxo species transformation and regulation by co-existing chloride: Reaction pathways and impacts on the generation of chlorinated by-products - Hongyu Zhou; Yong-li He; Jiali Peng; Xiaoguang Duan; Xiaohui Lu; Heng Zhang; Yang Liu; Chuan-shu He; Zhaokun Xiong; Tianyi Ma; Shaobin Wang; Bo Lai (Water Research, 2024)

Visualization of phenanthrene effect on biochar colloids transport in porous media - Ying Zhao; Da Fan; Jiabin Ma; Heng Li; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

A wearable strain sensor with self-cleaning capability for underwater applications - Jing Liu; Junze Zhang; Weiwei Sun; Yushu Qian; Jingge Liu; Heng Zhai; Zeyu Zhao; Kaili Chen; Yi Li; Gang Li (Chemical Engineering Journal, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Heterobimetallic praseodymium-nickel active sites with Pr-N4C2 and Ni-N4 moieties enabling synergistic catalysis of CO2 electroreduction - Heng Zhang; Yajie Cao; Min Sun; Yang Liu; Yan Wang; Haorun Li; Riguang Zhang; Xiaojun Gu; Shanghong Zeng (Chemical Engineering Journal, 2024)

H2 production from coal by enriching sugar fermentation and alkane oxidation with hyperthermophilic resistance microbes in municipal wastewater - Huaiwen Zhang; Yaojing Qiu; Tairan Liu; Xinya Yang; Ruixiao Yan; Heng Wu; Anjie Li; Jian Liu; Yahong Wei; Yiqing Yao (Chemical Engineering Journal, 2024)

Ferrate(VI)-based synergistic oxidation processes (Fe(VI)-SOPs): Promoted reactive species production, micropollutant/microorganism elimination, and toxicity reduction - Jie-Yu Cao; Ye Du; Xin Dai; Tong Liu; Zhong-Juan Wang; Jie Li; Heng Zhang; Peng Zhou; Bo Lai (Chemical Engineering Journal, 2024)

Effect of freeze-thaw cycles on the mechanical performance of wheat straw biomass ash modified soil - Zhengfa Chen; Xibin Liu; Quanmin Li; Heng Wu; Jiahao Zhang (Cold Regions Science and Technology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The Effect of Selenium on Endometrial Repair in Goats with Endometritis at High Cortisol Levels - Hanqing Li; Changning Yuan; Heng Wang; Luying Cui; Kangjun Liu; Long Guo; Jianji Li; Junsheng Dong (Biological Trace Element Research, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Mechanically treated Mn2O3 triggers peracetic acid activation for superior non-radical oxidation of micropollutants: Identification of reactive complexes - Yudan Dong; Chuan-Shu He; Si Sun; Jiali Liu; Zhi-Hui Xie; Jie-Yuan Li; Peng Zhou; Heng Zhang; Fan Dong; Bo Lai (Water Research, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Maximizing potato tuber yields and nitrogen use efficiency in semi-arid environments by precision fertilizer depth application - Nanhai Zhang; Haiqiang Luo; Heng Li; Mingwei Bao; Enke Liu; Weixing Shan; Xiaolong Ren; Zhikuan Jia; Kadambot H.M. Siddique; Peng Zhang (European Journal of Agronomy, 2024)

Immobilizing cobalt-iron bimetal on Al2O3 by electroless plating-calcination for peroxymonosulfate activation: Performance, mechanistic and practicality - Heng Zhang; Jia Zhao; Fan Liu; Jialong Yin; Wei Li; Xiaoqiang Dai; Peng Zhou; Yang Liu; Bo Lai (Chemical Engineering Journal, 2024)

Full-Color upconversion luminescence nanoplatform for real three-dimensional volumetric color displays - Heng Jia; Jia Zhao; Zhiqiang Huo; Xiaorui Feng; Weixia Liu; Shaohong Guo; Nan Li; Daguang Li; Yu Yang; Weiyan He; Yingyue Teng; Weiping Qin (Chemical Engineering Journal, 2024)

Coupling effect of vacancy defects and multi-adsorption sites in porous carbon cathode for high-performance aqueous zinc-ion hybrid capacitors - Heng-Xiang Li; Wen-Jing Shi; Ling-Yang Liu; Xiaohua Zhang; Peng-Fang Zhang; Qun Wang; Ying Liu; Zhao-Yang Wang; Jianmin Dou (Chemical Engineering Journal, 2024)

Nickel induces mitochondrial damage in renal cells in vitro and in vivo through its effects on mitochondrial biogenesis, fusion, and fission - Heng Yin; Xinglai Li; Chengbi Wang; Xiaocong Li; Jingbo Liu (Chemico-Biological Interactions, 2024)

A new monsoon circulation index defining precipitation variability in the East Asian summer monsoon northern marginal zone - Congxi Fang; Yu Liu; Huiming Song; Qiufang Cai; Heng Liu; Qiang Li; Changfeng Sun (Theoretical and Applied Climatology, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Enhanced removal of Pb2+ and Congo red from aqueous solutions using hierarchically porous melamine sponge/polyvinyl alcohol/Zr-MOF composites - Heng Zhao; Tianrui Li; Miaomiao Zhang; Xiujing Peng; Chengjin Xu; Jianhui Su; Zhen Yang; Xiaolei Liu; Guoxin Sun; Yu Cui (Journal of Environmental Chemical Engineering, 2024)

Synergistically accelerating capture and catalytic conversion of polysulfides by Co@NCNT-MoSe2 nanocomposite modified separator for advanced Lithium-Sulfur batteries - Xinwei Wang; Kangning Xu; Jiayi Guo; Zeyang Li; Siyang Liu; Lianshan Sun; Jianxun Zhao; Heng Liu; Wanqiang Liu; Fang Wang (Chemical Engineering Journal, 2024)

Calcium peroxide orchestrates virus-induced heavy metal resistome via shaping humeomics in sludge composting - Heng Lu; Shuaipeng Liu; Rixin Bao; Qunliang Li (Chemical Engineering Journal, 2024)

Cellulose nanofibers embedded chitosan/tannin hydrogel with high antibacterial activity and hemostatic ability for drug-resistant bacterial infected wound healing - Dangwei Li; Xiangyang Dong; Xia Liu; Heng Lin; Di Yang; Xiaowen Shi; Chaoji Chen; Fenghua Tao; Linbin Jiang; Hongbing Deng (Carbohydrate Polymers, 2024)

Cobalt-doped CdS quantum dots enhanced photoelectroreduction of CO2 to formic acid with high selectivity - Shengqi Liu; Zhenyan Guo; Ying Yang; Pei-dong Wu; Zhengyi Li; Keping Wang; Heng Zhang; Hu Li; Song Yang (Environmental Chemistry Letters, 2024)

Selenomethionine Inhibits NF-κB-mediated Inflammatory Responses of Bovine Mammary Epithelial Cells Caused by Klebsiella pneumoniae by Increasing Autophagic Flux - Siyan Xu; Yixue Miao; Junsheng Dong; Luying Cui; Kangjun Liu; Jianji Li; Xia Meng; Guoqiang Zhu; Heng Wang (Biological Trace Element Research, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Incorporating microbial inoculants to reduce nitrogen loss during sludge composting by suppressing denitrification and promoting ammonia assimilation - Xueling Liang; Xiaoli Wen; Hongmei Yang; Heng Lu; Ao Wang; Shuaipeng Liu; Qunliang Li (Science of The Total Environment, 2024)

Profiles and transplacental transfer of per- and polyfluoroalkyl substances in maternal and umbilical cord blood: A birth cohort study in Zhoushan, Zhejiang Province, China - Liangpo Liu; Peixia Yan; Xuan Liu; Junxia Zhao; Meiping Tian; Qingyu Huang; Jianbo Yan; Zhendong Tong; Yongli Zhang; Jie Zhang; Tongjie Zhang; Jianquan Guo; et al. (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Different survival strategies of the phosphate-mineralizing bacterium Enterobacter sp. PMB-5 in response to cadmium stress: Biomineralization, biosorption, and bioaccumulation - Huayan Huang; Keke Wang; Shiyao Li; Ke Liang; Jingtong Dai; Jiannan Jian; Yongyun Li; Huakang Liu; Heng Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

A Rapid Assessment Method for Flood Risk Mapping Integrating Aerial Point Clouds and Deep Learning - Xin Fang; Jie Wu; Peiqi Jiang; Kang Liu; Xiaohua Wang; Sherong Zhang; Chao Wang; Heng Li; Yishu Lai (Water Resources Management, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

PIMFP: An accurate tool for the prediction of intramuscular fat percentage in live pigs using ultrasound images based on deep learning - Zhen Liu; Heng Du; Feng-Dan Lao; Zhen-Cai Shen; Yi-Hang Lv; Lei Zhou; Li Jiang; Jian-Feng Liu (Computers and Electronics in Agriculture, 2024)

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Relocating selenium alkyl chain enables efficient all-small molecule organic solar cells - Gengsui Tian; Yulu Li; Yao Chen; Tainan Duan; Dingqin Hu; Peihao Huang; Qianqian Chen; Heng Liu; Haiyan Chen; Xinhui Lu; Shirong Lu; Zeyun Xiao (Chemical Engineering Journal, 2024)

Integration of transcriptome and metabolome reveals the accumulation of related metabolites and gene regulation networks during quinoa seed development - Qianchao Wang; Jirong Shi; Junna Liu; Ping Zhang; Li Li; Heng Xie; Hanxue Li; Hongxin Wang; Chenghong Liu; Peng Qin (Plant Molecular Biology, 2024)

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

Corrigendum to “Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus” [Aquaculture 578(15): 740130, 2024] - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Membrane-based technology in water and resources recovery from the perspective of water social circulation: A review - Hesong Wang; Jiaxuan Yang; Han Zhang; Jing Zhao; Hongzhi Liu; Jinlong Wang; Guibai Li; Heng Liang (Science of The Total Environment, 2024)

Synergistic effects of ultrasonication on the flotation separation of galena from chalcopyrite using sulfuric acid as a depressant - Qinbo Cao; Yanjun Li; Heng Zou; Dianwen Liu; Yan Yan; Haiyu Zhang (Minerals Engineering, 2024)

Enhanced Fenton-like oxidation (Vis/Fe(III)/Peroxydisulfate): The role of iron species and the Fe(III)-LVF complex in levofloxacin degradation - Afang Wang; Yang Shi; Yang Liu; Wei Li; Heng Zhang; Xiaoqiang Dai; Li Luo; Gang Yao; Bo Lai (Journal of Hazardous Materials, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

In-situ repairing quantum-dot-monolayer-film defects for laminated light-emitting diodes - Heng Lin; Yang Liu; Hailong Hu; Tailiang Guo; Fushan Li (Chemical Engineering Journal, 2024)

Stretchable triboelectric sensor array for real-time tactile sensing based on coaxial printing - Changgen Li; Xinyi Hu; Bin Liu; Shiyi Wang; Yuan Jin; Runhao Zeng; Heng Tang; Yong Tang; Xinrui Ding; Hui Li (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Initial soil moisture prewinter affects the freeze–thaw profile dynamics of a Mollisol in Northeast China - Yanru Wen; Bao Liu; Heng Jiang; Ting-Yong Li; Bin Zhang; Wenbin Wu (CATENA, 2024)

Cucumber seed polypeptides regulate RANKL-induced osteoclastogenesis through OPG/RANKL/RANK and NF-κB - Tao Yu; Xiao Liu; Meng Jiang; Yuanyue Li; Heng Su; Ben Niu (In Vitro Cellular & Developmental Biology - Animal, 2024)
Postmenopausal osteoporosis (PMOP) is a common disease that endangers the health of elderly women. Cucumber seeds have shown excellent therapeutic effects on PMOP, but the mechanism of cucumber seed peptide (CSP) remains unclear. The expression levels of NF-κB and osteoclast-related genes were detected by RT-qPCR. The levels of apoptosis-related proteins were detected by Western blotting. Nuclear translocation of NF-κB p65 and osteoclast formation were detected by immunofluorescence and tartrate-resistant acid phosphatase (TRAP) staining, respectively. ELISA was used to detect the expression levels of OPG, M-CSF, and RANKL. Hematoxylin–eosin (H&E) and TRAP staining were used to observe the effects of CSP on bone formation. In RAW264.7 cells, CSP (0.4 mg/L, 4 mg/L, and 40 mg/L) effectively inhibited the expression of osteoclast-related genes (Cathepsin-K, MT1-MMP, MMP-9, and TRAP). TRAP-positive multinucleated giant cells gradually decreased. Furthermore, NF-κB pathway activation downstream of RANK was inhibited. In bone marrow stromal cells (BMSCs), the expression levels of M-CSF and RANKL gradually decreased, and OPG gradually increased with increasing CSP concentrations. Treatment of RAW264.7 cells with pyrrolidine dithiocarbamate (PDTC, an inhibitor of NF-κB) prevented the formation of osteoclasts. Treatment with different concentrations of CSP effectively decreased the levels of RANKL and M-CSF in rat serum and increased the expression of OPG in the oophorectomy (OVX) rat model. Furthermore, different concentrations of CSP could ameliorate the loss of bone structure and inhibit the formation of osteoclasts in rats. CSP inhibits osteoclastogenesis by regulating the OPG/RANKL/RANK pathway and inhibiting the NF-kB pathway.

The impact of climate change and human activities on the change in the net primary productivity of vegetation—taking Sichuan Province as an example - Tangrui Dai; Xiaoai Dai; Heng Lu; Tao He; Weile Li; Cheng Li; Shengqi Huang; Yiyang Huang; Chenbo Tong; Ge Qu; Yunfeng Shan; Shuneng Liang; et al. (Environmental Science and Pollution Research, 2023)

Uptake, translocation, accumulation, and metabolism of fluroxypyr-meptyl and oxidative stress induction in rice seedling - Zhao Jie Chen; Hao Wen Wang; Si Ying Li; Yong Heng Zhang; Ya Nan Qu; Zhi Hai He; Xue Sheng Li; Xiao Liang Liu (Environmental Science and Pollution Research, 2023)

Cost-effective identification of the field maturity of tobacco leaves based on deep semi-supervised active learning and smartphone photograph - Tong Sun; Chaoqun Xue; Yang Chen; Luyao Zhao; Chenchen Qiao; Aoyu Huang; Feitao Li; Chao Liu; Heng Wang; Yongfeng Yang; Qian Yao; Gaojie Wang; et al. (Computers and Electronics in Agriculture, 2023)

Surface modification of FeⅢ-juglone coating on nanofiltration membranes for efficient biofouling mitigation - Jialin Song; Daliang Xu; Yonghui Han; Xuewu Zhu; Zihan Liu; Guibai Li; Heng Liang (Water Research, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

UPK1B promoted the invasion and stem cell characteristics of non-small cell lung cancer cells by modulating c-myc/Sox4 axis - Yiyang Liu; Li Ding; Chunwei Li; Lei Heng; Jianjun Chen; Yulong Hou (Tissue and Cell, 2023)

A semi-analytical model to estimate Chlorophyll-a spatial-temporal patterns from Orbita Hyperspectral image in inland eutrophic waters - Zhubin Zheng; Chao Huang; Yunmei Li; Heng Lyu; Changchun Huang; Na Chen; Ge Liu; Yulong Guo; Shaohua Lei; Runfei Zhang; Jianzhong Li (Science of The Total Environment, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Soil decreases N2O emission and increases TN content during combined composting of wheat straw and cow manure by inhibiting denitrification - Ruixiao Yan; Heng Wu; Xinya Yang; Chaozhi Yang; Hongyi Lyu; Huaiwen Zhang; Suqi Li; Tairan Liu; Ronghua Li; Yiqing Yao (Chemical Engineering Journal, 2023)

Identification and validation of major-effect quantitative trait locus QMS-5B associated with male sterility in photo-thermo-sensitive genic male sterile wheat - Fuqiang Niu; Zihan Liu; Fengting Zhang; Shaohua Yuan; Jianfang Bai; Yongjie Liu; Yanmei Li; Heng Zhang; Huishu Zhang; Changping Zhao; Xiyue Song; Liping Zhang (Theoretical and Applied Genetics, 2023)

Photocatalytic membrane coated with α-Fe2O3/Fe3O4 for enhanced filtration performance and antifouling property in surface water treatment - Yuanqing Guo; Quan Liu; Xiaobin Tang; Heng Liang; Guibai Li; Liwei Yang; Lu Wang; Xiaoling Li; Yan Sun (Chemosphere, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

Discovery of Michael reaction acceptors from the leaves of Ailanthus altissima by a modified tactic - Zhi-Kang Duan; Shan-Shan Guo; Li Ye; Zhi-Heng Gao; Dai Liu; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

A dual-carbon structured molybdenum selenide composites controlled via interface engineering and chemical bonding to attain high initial coulombic efficiency and rate capability of potassium-ion batteries - Shuangsheng Xiong; Shengmei Wang; Zheng Li; Zhengguang Zhang; Heng Liu; Jing Wang; Li Hou; Yuanzhe Wang; Faming Gao (Chemical Engineering Journal, 2023)

Fast deployable real-time bioelectric dissolved oxygen sensor based on a multi-source data fusion approach - Yongyun Li; Yahui Chen; Yi Chen; Renwei Qing; Xinyu Cao; Peng Chen; Wei Liu; Yao Wang; Guangwu Zhou; Heng Xu; Likai Hao; Can Wang; et al. (Chemical Engineering Journal, 2023)

Regulating sludge composting with percarbonate facilitated the methylation and detoxification of arsenic mediated via reactive oxygen species - Hongmei Yang; Xiaojing Chen; Ao Wang; Shuaipeng Liu; Xueling Liang; Heng Lu; Qunliang Li (Bioresource Technology, 2023)

Distribution of emergent aquatic vegetation leaf inclination angle and its simulation - Huaijing Wang; Yunmei Li; Xianzhang Dong; Junda Li; Huaiqing Liu; Xiaolan Cai; Jiafeng Xu; Gaolun Wang; Heng Lyu; Jianhong Li (Aquatic Botany, 2023)

DNA strand displacement and TdT-Mediated DNA extension for swift, convenient, and quantitative evaluation of sperm DNA integrity and its clinical implications - Bei Yan; Heng Fan; Hanxu Ji; Siqi Li; Hao Hu; Xiuli Gu; Shaotong Jia; Ying Liu; Jing Guo; Zhongzheng Yang; Lili Zhou; Xianjin Xiao; et al. (Analytica Chimica Acta, 2023)

Enhanced cadmium phytoextraction efficiency of ryegrass (Lolium perenne L.) by porous media immobilized Enterobacter sp. TY-1 - Yongyun Li; Yumei Zhang; Xianghan Chen; Yikai Liu; Shiyao Li; Huakang Liu; Heng Xu (Chemosphere, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Controlling ultrafiltration membrane fouling in surface water treatment via combined pretreatment of O3 and PAC: Mechanism investigation on impacts of technological sequence - Jiaxuan Yang; Yatao Liu; Jing Zhao; Hesong Wang; Guibai Li; Heng Liang (Science of The Total Environment, 2023)

Oxygen vacancies mediate the degradation of refractory organics in the interflow around a simple landfill: Based on Mg-Fe3O4/PMS system - Hengyi Liu; Lei Li; Heng Zhang; Jin Guo; Wenjie Ye; Guotao Liu; Xuya Peng (Journal of Environmental Chemical Engineering, 2023)

A systemic evaluation of aerobic granular sludge among granulation, operation, storage, and reactivation processes in an SBR - Jun Liu; Xushen Han; Xuewu Zhu; Jun Li; Dan Zhong; Liangliang Wei; Heng Liang (Environmental Research, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Transmission and regulation insights into antibiotic resistance genes in straw-sludge composting system amended with calcium peroxide - Heng Lu; Shuaipeng Liu; Ao Wang; Hongmei Yang; Xueling Liang; Xiaojing Chen; Qunliang Li (Bioresource Technology, 2023)

A tradeoff between denitrification and nitrate leaching into the subsoil in nitrate-rich vegetable soils treated by reductive soil disinfestation - Hui-Min Zhang; Yu Liu; Ying-Hua Zhang; Yong Li; Zhao-Xiong Chen; Xin Sun; Hang Jing; Jing Wang; Ahmed S. Elrys; Mao-Heng Zhang; Zu-Cong Cai; Yi Cheng (Agriculture, Ecosystems & Environment, 2023)

Surfactant enhanced thermally activated persulfate remediating PAHs-contaminated soil: Insight into compatibility, degradation processes and mechanisms - Wei Zhang; Wenjie Wu; Jianfei Wu; Xiaobin Liu; Jian Tian; Heng Li; Qingbiao Li; Yanmei Zheng (Chemosphere, 2023)

Current status of ecological compensation for Bohai Sea reclamation and management countermeasures - Wei Li; Qi Yue; Heng Hu; Liang Liu (Marine Policy, 2023)

Synergistic effect of potassium ferrate and ferrous iron for improving ultrafiltration performance in algae-laden water treatment - Yonghui Han; Jinlong Wang; Daliang Xu; Jialin Song; Hesong Wang; Xuewu Zhu; Xinsheng Luo; Liu Yang; Guibai Li; Heng Liang (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

Gender differences in thermal comfort under coupled environmental factors - Heng Du; Zisheng Zhao; Junmeng Lyu; Jinbo Li; Zhiqiang liu; Xiangyang Li; Yuxin Yang; Li Lan; Zhiwei Lian (Energy and Buildings, 2023)

Experimental Study on the Real-Time Stability Assessment Method for Unstable Sliding Rock - Yan Du; Jingnan Liu; Mowen Xie; Santos Daniel Chicas; Asim Farooq; Heng Li; Lize Ning (Rock Mechanics and Rock Engineering, 2023)

A programmable DNA nanodevice for colorimetric detection of DNA methyltransferase activity using functionalized hemin/G-quadruplex DNAzyme - Wenxu Yuan; Kaiting Xiao; Xingxing Liu; Yanming Lai; Fazeng Luo; Wei Xiao; Jinjun Wu; Pan Pan; Yongkui Li; Heng Xiao (Analytica Chimica Acta, 2023)

Selective elimination of sulfonamide antibiotics upon periodate/catechol process: Dominance of quinone intermediates - Shuai Yang; Yang Shi; Xinhao Wang; Yang Liu; Yi Ren; Wei Li; Heng Zhang; Xiaoqiang Dai; Weiyi Sun; Bo Lai (Water Research, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Spatial distribution of landslide shape induced by Luding Ms6.8 earthquake, Sichuan, China: case study of the Moxi Town - Xuemei Liu; Pengcheng Su; Yong Li; Zhaoxu Xia; Siyuan Ma; Rui Xu; Yao Lu; Dahu Li; Heng Lu; Renmao Yuan (Landslides, 2023)

Regulating the electrokinetic delivery of Tween 80 and persulfate for remediating low-permeability phenanthrene contaminated soil: Importance of reducing unproductive consumption - Wei Zhang; Heng Li; Siqiang Xiao; Jianfei Wu; Chuanhu Wang; Xiaobin Liu; Qingbiao Li; Yanmei Zheng (Process Safety and Environmental Protection, 2023)

Ship design optimization with mixed uncertainty based on evidence theory - Heng Li; Xiao Wei; Zuyuan Liu; Baiwei Feng; Qiang Zheng (Ocean Engineering, 2023)

Abrupt warming of the equatorial intermediate Pacific during Heinrich Stadial 1 - Shuai Zhang; Tiegang Li; Zhoufei Yu; Fengming Chang; Sifan Gu; Zhifang Xiong; Heng Liu; Fang Qian; Junru Zhang; Xuhua Cheng; Baohua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Ambient temperature exposure causes lung function impairment: The evidence from Controlled Temperature Study in Healthy Subjects (CTSHS) - Weihong Qiu; Heng He; Lieyang Fan; Xiaobing Feng; Minjing Li; Chaoqian Dong; Zhenzhen Li; Wei Liu; Ruyi Liang; Yingdie Zhang; Yongfang Zhang; Pei Gu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Strain-Hardening, impact protective and Self-Healing supramolecular polyurethane nanocomposites enabled by quadruple H-Bonding, disulfide bonds and nanoparticles - Ziwei Qin; Yi Yang; Qingli Tian; Hao-Yang Mi; Heng Li; Runhao Guo; Ying Wang; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

First report of root rot caused by Fusarium oxysporum on Knoxia valerianoides in China - Chunju Liu; Bin Qiu; Lei Zhang; Heng Li; Jiahong Dong; Xiahong He (Journal of Plant Pathology, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Birth-and-death evolution of ribonuclease 9 genes in Cetartiodactyla - Datian Lang; Xiaoping Wang; Chunbing Liu; Weihang Geng; David M. Irwin; Shanyuan Chen; Chunqing Li; Li Yu; Heng Xiao (Science China Life Sciences, 2023)

Theoretical and Numerical Studies of Rock-Support Interaction by Considering Imperfect Rock-Lining Interface - Mingyang Ren; Xuyang Wu; Junkui Pan; Heng Liu; Ningjing Li (Geotechnical and Geological Engineering, 2023)

A classification-based approach to mapping particulate organic matter (POM) in inland water using OLCI images - Huaiqing Liu; Wenyu Liu; Jie Lin; Heng Lyu; Yunmei Li; Fangfang Chen; Ying Zhao; Jiafeng Xu; Honglei Guo (Environmental Science and Pollution Research, 2023)

Distribution characteristics of microplastics in soil of Loess Plateau in northwest China and their relationship with land use type - Mengwei Zhang; Yu Zheng; Junlin Li; Kun Liu; Heng Wang; Hongcheng Gu; Zhenming Zhang; Xuetao Guo (Science of The Total Environment, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

New insights into interfacial interaction and nanoconfinement effect in synergistic oxidation-filtration via CoFe2O4-ceramic membrane activated peroxymonosulfate - Jiaxuan Yang; Langming Bai; Jing Zhao; Yatao Liu; Hesong Wang; Guibai Li; Heng Liang (Chemical Engineering Journal, 2023)

Underwater target detection algorithm based on improved YOLOv4 with SemiDSConv and FIoU loss function - Chengpengfei Zhang; Guoyin Zhang; Heng Li; Hui Liu; Jie Tan; Xiaojun Xue (Frontiers in Marine Science, 2023)
Underwater target detection is an indispensable part of marine environmental engineering and a fast and accurate method of detecting underwater targets is essential. Although many target detection algorithms have achieved great accuracy in daily scenes, there are issues of low-quality images due to the complex underwater environment, which makes applying these deep learning algorithms directly to process underwater target detection tasks difficult. In this paper, we presented an algorithm for underwater target detection based on improved You Only Look Once (YOLO) v4 in response to the underwater environment. First, we developed a new convolution module and network structure. Second, a new intersection over union loss was defined to substitute the original loss function. Finally, we integrated some other useful strategies to achieve more improvement, such as adding one more prediction head to detect targets of varying sizes, integrating the channel attention into the network, utilizing K-means++ to cluster anchor box, and utilizing different activation functions. The experimental results indicate that, in comparison with YOLOv4, our proposed algorithm improved the average accuracy of the underwater dataset detection by 10.9%, achieving 91.1%, with a detection speed of 58.1 frames per second. Therefore, compared to other mainstream target detection algorithms, it is superior and feasible for applications in intricate underwater environments.

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Emission characteristics of dioxin during solid waste co-processing in the Chinese cement industry - Xiaoyuan Li; Heng Zhang; Meijia Liu; Changhao Cui; Li Li; Shifang Wang; Dahai Yan; Yang Liao (Journal of Hazardous Materials, 2023)

Environment-friendly and efficient electrochemical degradation of sulfamethoxazole using reduced TiO2 nanotube arrays-based Ti membrane coated with Sb-SnO2 - Weichen Zeng; Han Zhang; Rui Wu; Luming Liu; Guibai Li; Heng Liang (Journal of Hazardous Materials, 2023)

Removal of Bisphenol A via peroxymonosulfate activation over graphite carbon nitride supported NiCx nanoclusters catalyst: Synergistic oxidation of high-valent nickel-oxo species and singlet oxygen - Junjie You; Junyi Li; Heng Zhang; Mengfan Luo; Bo Xing; Yi Ren; Yang Liu; Zhaokun Xiong; Chuanshu He; Bo Lai (Journal of Hazardous Materials, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Stratified assessment and warning regimen for prevention of acute adverse reactions to iodinated contrast media: results of 150,343 cases in a tertiary hospital - Heng Liu; Haiyan Qiu; Junling Liu; Lingru Wang; Li Zhao; Yaling Wang; Xue Li (Medical & Biological Engineering & Computing, 2023)
For contrast-enhanced CT examinations, there is a lack of comprehensive optimal management strategies of risk factors to reduce the risk of iodinated contrast media (ICM)–induced acute adverse reactions (AAR). Here, we determine the relationship between the rate of ICM-AAR and a stratified assessment and warning (SAW) regimen, which integrated risk identification, stratification, early warning, and prevention. A total of 120,822 cases in the conventional assessment period (58 years ± 15, 55.25% men) and 150,343 cases (58 years ± 14, 55.83% men) in the SAW period were enrolled. The results showed that the total AAR incidence in the SAW period (414/150,343, 0.28%) was lower than that in the conventional assessment period (506/120,822, 0.42%, P < 0.001), in which the proportion of AAR patients decreased by one-third. It mainly presented as decreases in mild and moderate reactions ( P < 0.001), and a decrease in the proportion of moderate AAR patients ( P = 0.001). Subgroup analysis showed lower mild and moderate AAR incidence in patients with different risk levels and with different ICM injection parameters following SAW regimen. We concluded that SAW regimen was associated with lower incidence of mild and moderate AAR, and decreased proportion of moderate AAR patients, which held potential for improved ICM safety. Graphical abstract

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

The research progress, hotspots, challenges and outlooks of solid-phase denitrification process - Heng Wu; Anjie Li; Xu Yang; Jingting Wang; Yiliang Liu; Guoqiang Zhan (Science of The Total Environment, 2023)

Applications of functional nanoparticle–stabilized surfactant foam in petroleum-contaminated soil remediation - Jia Liu; Wen-yan Li; Hong-xin Chen; Shuang-qiang Li; Li-heng Yang; Kai-ming Peng; Chen Cai; Xiang-feng Huang (Journal of Hazardous Materials, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Correction to: Blocking P2RX7 Attenuates Ferroptosis in Endothelium and Reduces HG-induced Hemorrhagic Transformation After MCAO by Inhibiting ERK1/2 and P53 Signaling Pathways - Chengli Liu; Qi Tian; Jianfeng Wang; Peibang He; Shoumeng Han; Yujia Guo; Chen Yang; Guijun Wang; Heng Wei; Mingchang Li (Molecular Neurobiology, 2023)

Blocking P2RX7 Attenuates Ferroptosis in Endothelium and Reduces HG-induced Hemorrhagic Transformation After MCAO by Inhibiting ERK1/2 and P53 Signaling Pathways - Chengli Liu; Qi Tian; Jianfeng Wang; Peibang He; Shoumeng Han; Yujia Guo; Chen Yang; Guijun Wang; Heng Wei; Mingchang Li (Molecular Neurobiology, 2023)

Correction: RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2023)

Migration characteristics of chromium and organic compounds released from waste leather fragments in soil under rainfall - Shan-shan Guo; Heng-bo Liu; Jia-li Li; Jin-yan Yang (Process Safety and Environmental Protection, 2023)

Regulating the solventized structure to achieve highly reversible zinc plating/stripping for dendrite-free Zn anode by sulfolane additive - Heng Cao; Xiaomin Huang; Yuanxia Li; Yu Liu; Qiaoji Zheng; Yu Huo; Ruyi Zhao; Jingxin Zhao; Dunmin Lin (Chemical Engineering Journal, 2023)

Reversible anionic redox and spinel-layered coherent structure enable high-capacity and long-term cycling of Li-rich cathode - Zhi Li; Heng Li; Shuang Cao; Wei Guo; Jiali Liu; Jiarui Chen; Changmeng Guo; Gairong Chen; Baobao Chang; Yansong Bai; Xianyou Wang (Chemical Engineering Journal, 2023)

Boosting oxygen reduction with coexistence of single-atomic Fe and Cu sites decorated nitrogen-doped porous carbon - Heng Liu; Luozhen Jiang; Yamin Wang; Xinxin Wang; Javid Khan; Yanlin Zhu; Jiamin Xiao; Lina Li; Lei Han (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Hemodynamic effects of intravenous bolus injection of iopromide 370 twice in abdominal contrast-enhanced CT and coronary CTA dual-site sequential examinations - Lingru Wang; Haiyan Qiu; Lan Chen; Heng Liu; Junling Liu; Ying Yang; Yueting Sun; Yang Deng; Heng Liu; Xue Li (Medical & Biological Engineering & Computing, 2023)

Geochemical characteristics of heavy metals of bedrock, soil, and tea in a metamorphic rock area of Guizhou Province, China - Qihang Li; Chaofeng Li; Lanjun Liu; Wang Heng; Cheng Chen; Jie Long; Xuefeng Wen (Environmental Science and Pollution Research, 2023)

The redevelopment mode selection framework for Third Front Brownfields in China - Guiwen Liu; Zekai Li; Qingye Han; Heng Zhang (Environmental Science and Pollution Research, 2022)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

Identification of sulfate‐reducing magnetotactic bacteria via a group‐specific 16S rDNA primer and correlative fluorescence and electron microscopy: Strategy for culture‐independent study - Jinhua Li; Peiyu Liu; Nicolas Menguy; Karim Benzerara; Jinling Bai; Xiang Zhao; Eric Leroy; Chaoqun Zhang; Heng Zhang; Jiawei Liu; Rongrong Zhang; Kelei Zhu; et al. (Environmental Microbiology, 2022)
Magnetotactic bacteria (MTB) biomineralize intracellular magnetic nanocrystals and swim along geomagnetic field lines. While few axenic MTB cultures exist, living cells can be separated magnetically from natural environments for analysis. The bacterial universal 27F/1492R primer pair has been used widely to amplify nearly full‐length 16S rRNA genes and to provide phylogenetic portraits of MTB communities. However, incomplete coverage and amplification biases inevitably prevent detection of some phylogenetically specific or non‐abundant MTB. Here, we propose a new formulation of the upstream 390F primer that we combined with the downstream 1492R primer to specifically amplify 1100‐bp 16S rRNA gene sequences of sulfate‐reducing MTB in freshwater sediments from Lake Weiyanghu, Xi'an, northwestern China. With correlative fluorescence in situ hybridization and scanning/transmission electron microscopy, three novel MTB strains (WYHR‐2, WYHR‐3 and WYHR‐4) from the Desulfobacterota phylum were identified phylogenetically and structurally at the single‐cell level. Strain WYHR‐2 produces bullet‐shaped magnetosome magnetite, while the other two strains produce both cubic/prismatic greigite and bullet‐shaped magnetite. Our results expand knowledge of bacterial diversity and magnetosome biomineralization of sulfate‐reducing MTB. We also propose a general strategy for identifying and characterizing uncultured MTB from natural environments.

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Amino acid transporter gene TaATLa1 from Triticum aestivum L. improves growth under nitrogen sufficiency and is down regulated under nitrogen deficiency - Heng Chen; Yingchun Liu; Jiazhen Zhang; Yifei Chen; Cuican Dai; Renmei Tian; Tianxiang Liu; Mingxun Chen; Guang Yang; Zhonghua Wang; Hongxia Li; Xinyou Cao; et al. (Planta, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Mutation of rpoS is Beneficial for Suppressing Organic Acid Secretion During 1,3-Propandiol Biosynthesis in Klebsiella pneumoniae - Shufan Dong; Xuxia Liu; Tianyu Chen; Xiaoqin Zhou; Shengming Li; Shuilin Fu; Heng Gong (Current Microbiology, 2022)

Changes in the Serum Concentrations of Essential Trace Metals in Patients with Benign and Malignant Breast Cancers - Bing Cao; Yutao Lei; Heng Xue; Yongming Liang; Yaqiong Liu; Qing Xie; Lailai Yan; Ligang Cui; Nan Li (Biological Trace Element Research, 2022)

Characterization on a Novel Rolled Leaves and Short Petioles Soybean Mutant Based on Seq-BSA and RNA-seq Analysis - Xue Wang; Changkai Liu; Bingjie Tu; Yansheng Li; Heng Chen; Qiuying Zhang; Xiaobing Liu (Journal of Plant Biology, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

Is there any difference on cyanobacterial blooms patterns between Lake Chaohu and Lake Taihu over the last 20 years? - Honglei Guo; Huaiqing Liu; Heng Lyu; Yingchun Bian; Suke Zhong; Yangyang Li; Song Miao; Ziqian Yang; Jiafeng Xu; Jing Cao; Yunmei Li (Environmental Science and Pollution Research, 2022)

Behavioural analysis and dynamic simulation of the debris flow that occurred in Ganluo County (Sichuan, China) on 30 August 2020 - Nuo-dong Li; Wei Liu; Jin-heng Zhao (Journal of Mountain Science, 2022)

Episodic Neoproterozoic extension-related magmatism in the Altyn Tagh, NW China: implications for extension and breakup processes of Rodinia supercontinent - Jiang-bo Hao; Chao Wang; Ji-heng Zhang; Liang Liu; Yong-sheng Gai; Hang Li; Zun-pu Yu; Joseph G Meert; Xiao-ping Long; Xiao-kui Sun; Shuai Zhang (International Geology Review, 2022)

A modified analytical method for flexural toppling of rock slopes - Xiaofan An; Heng Zhou; Guanghong Ju; Naifei Liu; Ning Li; Shengjie Di (Arabian Journal of Geosciences, 2022)

Mesorhizobium xinjiangense sp. nov., isolated from rhizosphere soil of Alhagi sparsifolia - Dong Meng; Yu-Ling Liu; Jun-Jie Zhang; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Heng Meng; Zong-Jun Du; Wei-Min Li; Qiang Li (Archives of Microbiology, 2022)

Enhanced photosynthetic nitrogen use efficiency and increased nitrogen allocation to photosynthetic machinery under cotton domestication - Zhang-Ying Lei; Heng Wang; Ian J. Wright; Xin-Guang Zhu; Ülo Niinemets; Zi-Liang Li; Dong-Sheng Sun; Ning Dong; Wang-Feng Zhang; Zhong-Li Zhou; Fang Liu; Ya-Li Zhang (Photosynthesis Research, 2021)

Humoral immune durability of IgG for anti-SARS-CoV-2 in the normal pregnant women in Wuhan, China - Hongwen Ma; Jing Peng; Ruobing Li; Xuan Zheng; Shiyao Wu; Heng Yin; Min Li; Liu Qin; Fei Tang; Yun Zhao (Immunologic Research, 2021)

A Novel Diarylethene-rhodamine Unit Based Chemosensor for Fluorimetric and Colorimetric Detection of Hg2+ - Xiumei Li; Xue Li; Heng Zhao; Huimin Kang; Congbin Fan; Gang Liu; Shouzhi Pu (Journal of Fluorescence, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Lipocalin-2-induced proliferative endoplasmic reticulum stress participates in Kawasaki disease-related pulmonary arterial abnormalities - Zhaoling Shi; Yue Yin; Chen Li; Hui Ding; Nan Mu; Yishi Wang; Shanshan Jin; Heng Ma; Manling Liu; Jie Zhou (Science China Life Sciences, 2021)

Optimal segmentation scale selection and evaluation of cultivated land objects based on high-resolution remote sensing images with spectral and texture features - Heng Lu; Chao Liu; Naiwen Li; Xiao Fu; Longguo Li (Environmental Science and Pollution Research, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Structural network performance for early diagnosis of spastic cerebral palsy in periventricular white matter injury - Haoxiang Jiang; Heng Liu; Tingting Huang; Liang Wu; Fan Wu; Congcong Liu; Miaomiao Wang; Chao Jin; Jian Yang; Xianjun Li (Brain Imaging and Behavior, 2021)

Landscape change in response to multiperiod glacial debris flows in Peilong catchment, southeastern Tibet - Zhang Wang; Kai-heng Hu; Chao Ma; Yong Li; Shuang Liu (Journal of Mountain Science, 2021)

RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2021)

High‐resolution distribution pattern of surface water nitrous oxide along a cruise track from the Okhotsk Sea to the western Arctic Ocean - Liyang Zhan; Jiexia Zhang; Zhangxian Ouyang; Ruibo Lei; Suqing Xu; Di Qi; Zhongyong Gao; Heng Sun; Yuhong Li; Man Wu; Jian Liu; Liqi Chen (Limnology and Oceanography, 2021)
Nitrous oxide in the surface water was measured using an automatic underway system, along with measurements of surface water pCO 2 , dissolved oxygen, salinity, temperature, and sea ice coverage, along a cruise track through the Bering Sea and Chukchi Sea to the Canadian Basin during the 7 th Chinese National Arctic Research Expedition. The results show that, overall, the regions along the cruise track are net sources of N 2 O to the atmosphere. Several N 2 O oversaturation maxima were observed along the cruise track, with an absolute maximum of approximately 60%. According to the hydrographic setting and the distribution patterns of pCO 2 , dissolved oxygen, and sea ice coverage in the study area, it was concluded that the N 2 O oversaturation maxima may result from hydrographic processes, such as mixing of different water masses, upwelling or convection, and possible production beneath the sea ice. Additionally, the lowest value of approximately 90% may result from dilution related to the melting of sea ice. An evaluation of the air–sea flux along the cruise track shows that the continental shelf and upwelling region are N 2 O sources, whereas the study area in the open Arctic Ocean does not show obvious source or sink characteristics.

Diverse phylogeny and morphology of magnetite biomineralized by magnetotactic cocci - Peiyu Liu; Yan Liu; Xiang Zhao; Andrew P. Roberts; Heng Zhang; Yue Zheng; Fuxian Wang; Lushan Wang; Nicolas Menguy; Yongxin Pan; Jinhua Li (Environmental Microbiology, 2021)
Summary Magnetotactic bacteria (MTB) are diverse prokaryotes that produce magnetic nanocrystals within intracellular membranes (magnetosomes). Here, we present a large‐scale analysis of diversity and magnetosome biomineralization in modern magnetotactic cocci, which are the most abundant MTB morphotypes in nature. Nineteen novel magnetotactic cocci species are identified phylogenetically and structurally at the single‐cell level. Phylogenetic analysis demonstrates that the cocci cluster into an independent branch from other Alphaproteobacteria MTB, that is, within the Etaproteobacteria class in the Proteobacteria phylum. Statistical analysis reveals species‐specific biomineralization of magnetosomal magnetite morphologies. This further confirms that magnetosome biomineralization is controlled strictly by the MTB cell and differs among species or strains. The post‐mortem remains of MTB are often preserved as magnetofossils within sediments or sedimentary rocks, yet paleobiological and geological interpretation of their fossil record remains challenging. Our results indicate that magnetofossil morphology could be a promising proxy for retrieving paleobiological information about ancient MTB.

Geochemical Characteristics of Heavy Metals in Soil and Blueberries of the Core Majiang Blueberry Production Area - Qihang Li; Chaofeng Li; Heng Wang; Xiao Wei; Yuansheng Liu; Ruidong Yang; Xuefeng Wen (Bulletin of Environmental Contamination and Toxicology, 2021)

A complex gas hydrate system imaged jointly using MCS and OBS data from the northern South China Sea - Bin Liu; Xiangchun Wang; Yunxia Xu; Pengfei Wen; Liqing Li; Heng Zhang (Marine Geophysical Research, 2020)

Simulation and verification of an air-gun array wavelet in time-frequency domain based on van der waals gas equation - Dong Zhang; Huai-shan Liu; Lei Xing; Qian-qian Li; Xue-qin Liu; Jia Wei; Jian-hua Wang; Heng Zhou; Xin-min Ge (Applied Geophysics, 2020)

Remote estimation of total phosphorus concentration in the Taihu Lake using a semi-analytical model - Chenggong Du; Yunmei Li; Heng Lyu; Naisen Liu; Zhubin Zheng; Yuan Li (International Journal of Remote Sensing, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Single B cells reveal the antibody responses of rhesus macaques immunized with an inactivated enterovirus D68 vaccine - Huiwen Zheng; Zening Yang; Bingxiang Li; Heng Li; Lei Guo; Jie Song; Dongpei Hou; Nan Li; Jinxi Yang; Qiongwen Wu; Ming Sun; Longding Liu (Archives of Virology, 2020)

Two new quinolone alkaloids from the nearly ripe fruits of Tetradium ruticarpum - Yi-Heng Li; Xiao Liu; Min Yin; Fei Liu; Bi Wang; Xu Feng; Qi-Zhi Wang (Natural Product Research, 2020)

Association of Polygenic Risk Score with Age at Onset and Cerebrospinal Fluid Biomarkers of Alzheimer’s Disease in a Chinese Cohort - Wei-Wei Li; Zhen Wang; Dong-Yu Fan; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Ling Li; Heng Yang; Yu-Hui Liu; Xian-Le Bu; Wang-Sheng Jin; Fan Zeng; et al. (Neuroscience Bulletin, 2020)

Gene transfer and nucleotide sequence evolution by Gossypium cytoplasmic genomes indicates novel evolutionary characteristics - Ting-Ting Zhang; Heng Liu; Qi-Yuan Gao; Ting Yang; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Plant Cell Reports, 2020)

Characterization of Pseudomonas syringae pv. actinidiae Biovar 3 strain and cultivar tolerance to kiwifruit bacterial canker in China - Zhen-feng Ye; Peng-fei Wei; Shi-zhou Xue; Pu Liu; Bing Jia; Wei Heng; Li-wu Zhu (Journal of Plant Pathology, 2020)

Aspergillolide, a new 12-membered macrolide from sea cucumber-derived fungus Aspergillus sp. S-3-75 - Jun-Jie Tan; Xiao-Yu Liu; Yang Yang; Feng-Hua Li; Chang-Heng Tan; Yi-Ming Li (Natural Product Research, 2020)

The lifestyle transition of Arthrobotrys oligospora is mediated by microRNA-like RNAs - Xinglai Ji; Heng Li; Weihua Zhang; Jiai Wang; Lianming Liang; Chenggang Zou; Zefen Yu; Shuqun Liu; Ke-Qin Zhang (Science China Life Sciences, 2020)

Failure mechanism and dynamic processes of rock avalanche occurrence in Chengkun railway, China, on August 14, 2019 - Lei Zhu; Heng Liang; Siming He; Wei Liu; Qingyun Zhang; Gang Li (Landslides, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

IGS real-time service for global ionospheric total electron content modeling - Zishen Li; Ningbo Wang; Manuel Hernández-Pajares; Yunbin Yuan; Andrzej Krankowski; Ang Liu; Jiuping Zha; Alberto García-Rigo; David Roma-Dollase; Heng Yang; Denis Laurichesse; Alexis Blot (Journal of Geodesy, 2020)

Overexpression of the pear PbSPMS gene in Arabidopsis thaliana increases resistance to abiotic stress - Xianghong Jiang; Junyu Zhan; Qi Wang; Xinyi Wu; Xiaonan Chen; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu; Wei Heng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The study of ultrasound and iontophoresis on oxaprozin transdermal penetration using surface-enhanced Raman spectroscopy - Shupeng Liu; Xiang Bao; Songpo Zhang; Heng Zhang; Xiaofeng Lu; Taihao Li; Zhenyi Chen; Na Chen (Drug Delivery and Translational Research, 2020)

Paleoseismologic record of earthquakes along the Wuzunxiaoer section of the Altyn Tagh fault and its implication for cascade rupture behavior - Zhaode Yuan; Jing Liu-Zeng; You Zhou; Zhigang Li; Heng Wang; Wenqian Yao; Longfei Han (Science China Earth Sciences, 2020)

Spatiotemporal soil moisture variations associated with hydro‐meteorological factors over the Yarlung Zangbo River basin in Southeast Tibetan Plateau - Xueying Li; Liu Liu; Hao Li; Shuping Wang; Jingxia Heng (International Journal of Climatology, 2020)
Soil moisture (SM) is a key factor in the exchanging process of the hydrological cycle, which is rather difficult to be directly observed. In situ measurements on SM, however, are subjected to the point scales. Use of land surface models has been a promising way to explore SM variations, especially for poorly gauged high mountain regions such as the Yarlung Zangbo River (YZR) basin located in Southeast Tibetan Plateau. This study made an attempt to investigate the spatiotemporal variations of SM and discuss hydro‐meteorological factors impacting SM evolution based on the Global Land Data Assimilation Systems (GLDAS) outputs during the period 1970–2009. Results show that (a) GLDAS data sets have high agreement and low bias with in situ measurements and consistent spatial distribution with ERA reanalysis data sets; (b) an abrupt change of SM is detected in 1992 and a significantly decreasing trend happens during 1970–2009 and 1993–2009; (c) precipitation is the dominant climatic factor controlling SM during the period 1970–2009, whereas surface air temperature is the critical factor for the significant change of SM. Owing to the significant increasing of surface air temperature since 1992, its impact on SM increased by ∼91% than that before 1992. Evapotranspiration (ET) and snow water equivalent (SWE) are also taken into consideration, showing relatively weak influence on SM, which may be due to the dynamic process of coupled SM‐ET or low snow cover area fraction across the YZR basin. Findings in this study have important implications for SM variations in poorly gauged high mountain regions which may largely influences downstream water availability.

Quorum-sensing based small RNA regulation for dynamic and tuneable gene expression - Shao-Heng Bao; Wen-Ying Li; Chang-Jun Liu; Dong-Yi Zhang; Er Meng (Biotechnology Letters, 2019)

Petrogenesis of early Late Cretaceous Asa-intrusive rocks in central Tibet, western China: post-collisional partial melting of thickened lower crust - An-Bo Luo; Ming Wang; Cai Li; Chao-Ming Xie; Jian-jun Fan; Tian-Yu Zhang; Jin-Heng Liu; Wei Wang (International Journal of Earth Sciences, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Development of attenuated erythromycin‐resistant Streptococcus agalactiae vaccine for tilapia ( Oreochromis niloticus ) culture - Ling Liu; Dan‐Qi Lu; Jun Xu; Heng‐Li Luo; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is an important pathogen in fish, causing great losses of intensive tilapia farming. To develop a potential live attenuated vaccine, a re‐attenuated S. agalactiae (named TFJ‐ery) was developed from a natural low‐virulence S. agalactiae strain TFJ0901 through selection of resistance to erythromycin. The biological characteristics, virulence, stability and the immunization protective efficacy to tilapia of TFJ‐ery were determined. The results indicated that TFJ‐ery grew at a slower rate than TFJ0901. The capsule thickness of TFJ‐ery was significantly less ( p 0.05) than TFJ0901. When Nile tilapia were intraperitoneally (IP) injected with TFJ‐ery, the mortality of fish was decreased than that injected with TFJ0901. The RPS of fish immunized with TFJ‐ery at a dose of 5.0 × 10 7 CFU was 95.00%, 93.02% and 100.00% at 4, 8 and 16 weeks post‐vaccination, respectively. ELISA results showed that the vaccinated fish produced significantly higher ( p 0.05) antibody titres compared to those of control at 2 or 4 weeks post‐vaccination. Taken together, our results suggest that erythromycin could be used to attenuate S. agalactiae , and TFJ‐ery is a potent attenuated vaccine candidate to protect tilapia against S. agalactiae infections.

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Phthalate exposure and cumulative risk in a Chinese newborn population - Xueyan Li; Liangpo Liu; Heng Wang; Xueqin Zhang; Tonghu Xiao; Heqing Shen (Environmental Science and Pollution Research, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

RNA sequencing and SSR marker development for genetic diversity research in Woonyoungia septentrionalis (Magnoliaceae) - Meng Xu; Zhiting Li; Jianwen Wang; Sian Liu; Heng Cai (Conservation Genetics Resources, 2018)

Physical processes controlling earlier and later onset of a typhoon season in the western North Pacific - Heng Zuo; Tim Li; Jia Liu; Melinda Peng (Climate Dynamics, 2018)

The Middle Triassic evolution of the Bangong–Nujiang Tethyan Ocean: evidence from analyses of OIB-type basalts and OIB-derived phonolites in northern Tibet - Jian-Jun Fan; Cai Li; Jin-Heng Liu; Ming Wang; Yi-Ming Liu; Chao-Ming Xie (International Journal of Earth Sciences, 2018)

Comparison Study of Bone Defect Healing Effect of Raw and Processed Pyritum in Rats - Xingyu Zhu; Qianqian Gao; Genhua Zhao; Heng Wang; Ling Liu; Zhipeng Chen; Yijun Chen; Li Wu; Zisheng Xu; Weidong Li (Biological Trace Element Research, 2018)

A quasi single-phase model for debris flows and its comparison with a two-phase model - Chun-chen Xia; Ji Li; Zhi-xian Cao; Qing-quan Liu; Kai-heng Hu (Journal of Mountain Science, 2018)

BcMF11 and its homologous sequences may form a lncRNA family in Brassica diploids - Fang Zhang; Heng Dong; Yanhong Liu; Yaoyao Feng; Dong Zhou; Li Huang (Acta Physiologiae Plantarum, 2018)

Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean - Tian-Yu Zhang; Jian-Jun Fan; Cai Li; Chao-Ming Xie; Ming Wang; Yan-Wang Wu; Meng-Jing Xu; Wei Xu; Jin-Heng Liu; An-Bo Luo (International Geology Review, 2018)

Identification of a novel reassortant A (H9N6) virus in live poultry markets in Poyang Lake region, China - Heng Zhang; Mingbin Liu; Xiaoxu Zeng; Xiang Zhao; Zhiqiang Deng; Lei Yang; Wenbing Chen; Zi Li; Ming Jiao; Wen Xia; Bin Han; Haiying Chen; et al. (Archives of Virology, 2017)

Comprehensive risk assessment and source identification of selected heavy metals (Cu, Cd, Pb, Zn, Hg, As) in tidal saltmarsh sediments of Shuangtai Estuary, China - Chang-Fa Liu; Bing Li; Yi-Ting Wang; Yuan Liu; Heng-Jiang Cai; Hai-Feng Wei; Jia-Wen Wu; Jin Li (Environmental Monitoring and Assessment, 2017)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

Numerical analysis of the flow field in a sloshing tank with a horizontal perforated plate - Heng Jin; Yong Liu; Huajun Li; Qiang Fu (Journal of Ocean University of China, 2017)

Cultivated land information extraction in UAV imagery based on deep convolutional neural network and transfer learning - Heng Lu; Xiao Fu; Chao Liu; Long-guo Li; Yu-xin He; Nai-wen Li (Journal of Mountain Science, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

An isotope study of the accumulation mechanisms of high-sulfur gas from the Sichuan Basin, southwestern China - WenHui Liu; Tenger; ZhongNing Zhang; HouYong Luo; DianWei Zhang; Jie Wang; LiWu Li; Bo Gao; LongFei Lu; Heng Zhao (Science China Earth Sciences, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

The role of polyamines during exocarp formation in a russet mutant of ‘Dangshansuli’ pear (Pyrus bretschneideri Rehd.) - Wei Heng; Ziteng Wang; Xianghong Jiang; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu (Plant Cell Reports, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

What controls early or late onset of tropical North Atlantic hurricane season? - Heng Zuo; Tim Li; Jia Liu; Melinda Peng (Journal of Meteorological Research, 2016)

QTL mapping for salt tolerance at seedling stage in the interspecific cross of Gossypium tomentosum with Gossypium hirsutum - George Oluoch; Juyun Zheng; Xingxing Wang; Muhammad Kashif Riaz Khan; Zhongli Zhou; Xiaoyan Cai; Chunying Wang; Yuhong Wang; Xueyuan Li; Heng Wang; Fang Liu; Kunbo Wang (Euphytica, 2016)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

proBDNF Attenuates Hippocampal Neurogenesis and Induces Learning and Memory Deficits in Aged Mice - Jia Chen; Cheng-Ren Li; Heng Yang; Juan Liu; Tao Zhang; Shu-Sheng Jiao; Yan-Jiang Wang; Zhi-Qiang Xu (Neurotoxicity Research, 2016)

Remanufacturing cathode from end-of-life of lithium-ion secondary batteries by Nd:YAG laser radiation - Wei-wei Liu; Heng Zhang; Li-hong Liu; Xiao-chuan Qing; Zi-jue Tang; Ming-zheng Li; Jin-song Yin; Hong-chao Zhang (Clean Technologies and Environmental Policy, 2016)

A modified thymosin alpha 1 inhibits the growth of breast cancer both in vitro and in vivo: suppressment of cell proliferation, inducible cell apoptosis and enhancement of targeted anticancer effects - Xingzhen Lao; Bin Li; Meng Liu; Chen Shen; Tingting Yu; Xiangdong Gao; Heng Zheng (Apoptosis, 2015)

Characterization and classification of one new cytoplasmic male sterility (CMS) line based on morphological, cytological and molecular markers in non-heading Chinese cabbage (Brassica rapa L.) - Shuangping Heng; Dianyi Shi; Zhenhua Hu; Tao Huang; Jinping Li; Liyan Liu; Chunxiu Xia; Zhenzhen Yuan; Yuejin Xu; Tingdong Fu; Zhengjie Wan (Plant Cell Reports, 2015)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

Segmentation of high spatial resolution remote sensing images of mountainous areas based on the improved mean shift algorithm - Heng Lu; Chao Liu; Nai-wen Li; Jia-wei Guo (Journal of Mountain Science, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

Post-earthquake rainfall-triggered slope stability analysis in the Lushan area - Zhi-hua Yang; Heng-xing Lan; Hong-jiang Liu; Lang-ping Li; Yu-ming Wu; Yun-shan Meng; Liang Xu (Journal of Mountain Science, 2015)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

Differentially expressed genes related to the formation of russet fruit skin in a mutant of ‘Dangshansuli’ pear (Pyrus bretchnederi Rehd.) determined by suppression subtractive hybridization - Wei Heng; Li Liu; Meng-dong Wang; Bing Jia; Pu Liu; Zhen-feng Ye; Li-wu Zhu (Euphytica, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Comparison of Hydrolysis Efficiency and Enzyme Adsorption of Three Different Cellulosic Materials in the Presence of Poly(ethylene Glycol) - Min Zhang; Jia Ouyang; Baotian Liu; Heng Yu; Ting Jiang; Cong Cai; Xin Li (BioEnergy Research, 2013)

The anti-tumor effect and increased tregs infiltration mediated by rAAV-SLC vector - Rilun Li; Heng Hu; Huiying Ma; Long Chen; Shuang Zhou; Binbin Liu; Yinkun Liu; Chunmin Liang (Molecular Biology Reports, 2013)

Drought stress induces oxidative stress and the antioxidant defense system in ascorbate-deficient vtc1 mutants of Arabidopsis thaliana - Yue Niu; Yuping Wang; Ping Li; Feng Zhang; Heng Liu; Guochang Zheng (Acta Physiologiae Plantarum, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Heterologous interactions between NS1 proteins from different influenza A virus subtypes/strains - WeiZhong Li; Heng Zhang; GeFei Wang; Chi Zhang; XiangXing Zeng; Hui Liu; XiaoXuan Chen; YanXuan Xu; KangSheng Li (Science China Life Sciences, 2012)

Evaluating the prevalence and molecular epidemiology of echovirus 11 isolated from sewage in Shandong Province, China in 2010 - Jing Yang; Ning Cui; Haiyan Wang; Zexin Tao; Yao Liu; Heng Zhang; Hiromu Yoshida; Yanyan Song; Yong Zhang; Lizhi Song; Yan Li; Xiaojuan Lin; et al. (Virus Genes, 2012)

A comparative study of the characteristics of two Coxsackie A virus type 16 strains (genotype B) - ErXia Yang; Heng Zhao; Ying Zhang; JianSheng Liu; Yun Liao; LiChun Wang; PingFang Cui; LiXian Yang; LongDing Liu; ChengHong Dong; ShaoZhong Dong; CongWen Shao; et al. (Science China Life Sciences, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Small heat shock protein LimHSP16.45 protects pollen mother cells and tapetal cells against extreme temperatures during late zygotene to pachytene stages of meiotic prophase I in David Lily - Changjun Mu; Shaobo Wang; Shijia Zhang; Jiajia Pan; Ni Chen; Xiaofeng Li; Zhaoyan Wang; Heng Liu (Plant Cell Reports, 2011)

Simultaneous Effects of Lead and Cadmium on Primary Cultures of Rat Proximal Tubular Cells: Interaction of Apoptosis and Oxidative Stress - Lin Wang; Heng Wang; Jingui Li; Dawei Chen; Zongping Liu (Archives of Environmental Contamination and Toxicology, 2011)

The management and planning of citrus orchards at a regional scale with GIS - Wei Wu; Hong-Bin Liu; Heng-Lin Dai; Wei Li; Peng-Shou Sun (Precision Agriculture, 2011)

F-box Protein Arabidillo-1 Promotes Lateral Root Development by Depressing the Functioning of GA3 in Arabidopsis - Changjun Mu; Ni Chen; Xiaofeng Li; Pengfei Jia; Zhaoyan Wang; Heng Liu (Journal of Plant Biology, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Developmental characteristics of floral organs and pollen of Chinese cabbage (Brassica campestris L. ssp. chinensis) - Li Huang; Xiaofeng Zhao; Tingting Liu; Heng Dong; Jiashu Cao (Plant Systematics and Evolution, 2010)

Validation of Candidate Reference Genes for the Accurate Normalization of Real-Time Quantitative RT-PCR Data in Rice During Seed Development - Qian-Feng Li; Samuel S. M. Sun; Ding-Yang Yuan; Heng-Xiu Yu; Ming-Hong Gu; Qiao-Quan Liu (Plant Molecular Biology Reporter, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Erratum to: Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Identification of Sp1-elements in the promoter region of human homeobox gene NKX3.1 - Chun-xiao Yu; Tong Jin; Wei-wen Chen; Peng-ju Zhang; Wen-wen Liu; Heng-yun Guan; Ju Zhang; Qing-wei Liu; An-li Jiang (Molecular Biology Reports, 2009)

Ostryopsis davidiana seedlings inoculated with ectomycorrhizal fungi facilitate formation of mycorrhizae on Pinus tabulaeformis seedlings - Shu-Lan Bai; Guo-Lei Li; Yong Liu; R. Kasten Dumroese; Rui-Heng Lv (Mycorrhiza, 2009)

Influence of ginsenoside Rg1, a panaxatriol saponin from Panax notoginseng, on renal fibrosis in rats with unilateral ureteral obstruction - Xi-sheng Xie; Man Yang; Heng-cuang Liu; Chuan Zuo; Zi Li; Yao Deng; Jun-ming Fan (Journal of Zhejiang University-SCIENCE B, 2008)

Quercetin relieves chronic lead exposure-induced impairment of synaptic plasticity in rat dentate gyrus in vivo - Pu Hu; Ming Wang; Wei-Heng Chen; Ji Liu; Liang Chen; Shu-Ting Yin; Wu Yong; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Regulation of Paracellular Absorption of Cimetidine and 5-Aminosalicylate in Rat Intestine - Simon Yuji Zhou; Nusara Piyapolrungroj; Li-heng Pao; Cheng Li; Guangyu Liu; Ellen Zimmermann; David Fleisher (Pharmaceutical Research, 1999)